Protective film forming composition for alkaline hydrogen peroxide solution, substrate for semiconductor device manufacturing, and protective film forming method
By using a polymer containing an imide group as a protective film formation composition, the problems of substrate corrosion resistance and wet etching liquid resistance under high temperature conditions during the semiconductor device manufacturing process are solved, and efficient semiconductor device manufacturing is achieved.
Patent Information
- Application Number
- CN202310058295.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-12
- Filing Date
- 2023-01-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-01-19
AI Technical Summary
During the manufacturing process of existing semiconductor devices, it is difficult to maintain the corrosion resistance of the substrate and the resistance of the wet etching liquid under high temperature conditions, resulting in a decrease in yield.
An imide group-containing polymer is used as a protective film forming composition, which hardens under film formation conditions in a passive gas, and has high heat resistance, landfill/planarization characteristics and alkaline hydrogen peroxide water resistance.
The corrosion resistance of the substrate and the resistance of the wet etching liquid under high temperature conditions are achieved, and the manufacturing yield of the semiconductor device is improved.
Smart Images

Figure BDA0004060845240000071 
Figure BDA0004060845240000072 
Figure BDA0004060845240000081
Abstract
Description
Technical Field
[0001] The present invention relates to a protective film forming composition for providing a protective film that is resistant to a wet etching solution used in a semiconductor device manufacturing step, a substrate for semiconductor device manufacturing using the composition, a protective film forming method, and a pattern forming method using a multilayer resist method. Background Art
[0002] In the past, the high integration and high speed of semiconductor devices were achieved by miniaturizing the pattern size by shortening the wavelength of the light source using the photolithography technology (optical lithography) that uses light exposure as a general technology. In order to form such a fine circuit pattern on the semiconductor device substrate (processed substrate), a method of processing the processed substrate by dry etching is usually used, using a photoresist film with a pattern as an etching mask. However, in reality, there is no dry etching method that can obtain complete etching selectivity between the photoresist film and the processed substrate, so in recent years, substrate processing using a multilayer resist method has become generalized. This method is to insert an intermediate film that has a different etching selectivity from the photoresist film (hereinafter referred to as the resist upper film) between the resist upper film and the processed substrate, and after the resist upper film obtains a pattern, the resist upper film pattern is used as a dry etching mask, and the pattern is transferred to the intermediate film by dry etching, and then the intermediate film is used as a dry etching mask, and the pattern is transferred to the processed substrate by dry etching.
[0003] One of the multilayer resist methods is a three-layer resist method that can be performed using a general resist composition used in the single-layer resist method. This method is to form an organic lower film (hereinafter referred to as an organic film) by coating and calcining an organic lower film material composed of a composition containing an organic resin on a substrate to be processed, and then coating and calcining a resist intermediate film material composed of a composition containing a silicon-containing resin to form a silicon-containing film (hereinafter referred to as a silicon intermediate film), and then forming a general organic photoresist film (hereinafter referred to as a resist upper film) thereon. After the resist upper film is patterned, if dry etching is performed using fluorine-based gas plasma, the organic resist upper film can obtain a good etching selectivity ratio with respect to the silicon intermediate film, so the resist upper film pattern can be transferred to the silicon intermediate film. According to this method, even if a resist upper layer film that does not have a sufficient film thickness for directly processing a substrate to be processed or a resist upper layer film that does not have sufficient dry etching resistance for processing the substrate to be processed is used, the pattern can still be easily transferred to the silicon intermediate film because the silicon intermediate film is generally of the same or less film thickness than the resist upper layer film. If the silicon intermediate film to which the pattern has been transferred is subsequently used as a dry etching mask and the pattern is transferred to the organic lower film by dry etching using oxygen or hydrogen gas plasma, the pattern can be transferred to the organic lower film with sufficient dry etching resistance for processing the substrate. The pattern of the organic lower film to which the pattern has been transferred can be transferred to the substrate by dry etching using fluorine gas, chlorine gas, etc.
[0004] On the other hand, the miniaturization in the manufacturing steps of semiconductor devices has gradually approached the inherent limit of the wavelength of the light source used for optical lithography. Therefore, in recent years, some people have explored the high integration of semiconductor devices that do not rely on miniaturization. One of the methods is to explore semiconductor devices with complex structures such as multi-gate structures, and some of them have been put into practical use. When forming such a structure by a multilayer resist method, an organic film material can be used that can fill the holes, trenches, fins and other tiny patterns formed on the processed substrate with a film without gaps, or fill the height difference, pattern-dense parts and non-patterned areas with a film to flatten (planarization). By using such an organic film material to form a flat organic lower film surface on a high-low difference substrate, the film thickness variation of the silicon intermediate film and the resist upper film formed thereon can be suppressed, and the focus margin of optical lithography and the tolerance reduction in the subsequent processing steps of the processed substrate can be suppressed. In this way, semiconductor devices can be manufactured with good yields. On the other hand, in the single-layer resist method, in order to fill the processed substrate with height differences and patterns, the thickness of the upper resist film will be thickened, which will lead to pattern collapse after exposure and development, reflection from the substrate during exposure causing degradation of the pattern shape, etc. The pattern formation margin during exposure becomes narrower, making it difficult to manufacture semiconductor devices with good yield.
[0005] As mentioned above, the organic film material needs to be processed by dry etching to form a pattern with a high aspect ratio, so the organic film requires not only the above-mentioned filling and flattening performance, but also high dry etching resistance. Furthermore, the silicon intermediate film on the organic film also requires high dry etching resistance, so an inorganic hard mask formed by CVD, ALD method, etc., which has higher dry etching resistance than the silicon intermediate film formed by spin coating, is often selected as the silicon intermediate film. The temperature when forming this hard mask is usually above 300°C, so the organic film is also required to have high heat resistance that can withstand this temperature. In addition, when the inorganic hard mask is formed by CVD and ALD methods, peeling sometimes occurs between the substrate and the processed substrate, so it is also required to have a good adhesion to the processed substrate. It becomes important for organic film materials with excellent processing margin to have these properties.
[0006] In addition, as for the method of increasing the speed of the next generation of semiconductor devices, some people have begun to explore the use of new materials with high electron mobility, such as strained silicon, gallium arsenide, and precision materials such as ultra-thin film polysilicon that can be controlled in angstrom units. However, when a substrate to be processed using such new precision materials is formed under the conditions of the above-mentioned flattening film formed using the organic lower film material, such as the film forming conditions in the air at 300°C or above, the material will be corroded by oxygen in the air, and the high speed of the semiconductor device cannot exert the performance as designed by the material, and it may not be possible to achieve the expected yield in industrial production. Therefore, in order to avoid the yield reduction caused by the corrosion of the substrate by the air under such high temperature conditions, it is expected that there will be an organic lower film material that can be formed in a passive gas. In addition, it is sometimes necessary to use wet etching using chemicals to process the substrate, so at this time, the organic lower film that serves as the processing mask is also required to be resistant to the wet etching solution.
[0007] Here, regarding the multilayer resist method, the ideal background of materials that respond to wet etching processing is described in detail. In order to improve the performance of semiconductor devices, the most advanced semiconductor devices use technologies such as three-dimensional transistors and through wiring. In the patterning step used to form the structure in such a semiconductor device, patterning using the above-mentioned multilayer resist method is implemented. In such patterning, after the pattern is formed, a step of removing the silicon intermediate film without damaging the pattern is sometimes required. When this removal is insufficient, that is, when the wafer is moved to the next step of manufacturing processing while the cleaning object remains, the device manufacturing yield will indeed decrease. In this way, with the miniaturization of components, the cleanliness required for the cleaning step increases. However, the main constituent elements of the silicon intermediate film and the main constituent elements of the semiconductor device substrate in the past are often silicon. Even if the silicon intermediate film is selectively removed by dry etching, the constituent components are similar, and it is difficult to suppress damage to the semiconductor device substrate. This problem cannot be solved even by conventional wet etching using a hydrofluoric acid stripping solution. Some people consider using alkaline hydrogen peroxide solution called SC1 (Standard Clean-1) generally used in semiconductor manufacturing as a wet etching solution for stripping solution that does not damage the semiconductor device substrate. In this case, the organic lower layer film needs to be resistant to alkaline hydrogen peroxide solution.
[0008] In addition, some people have studied the process of wet etching a substrate such as titanium nitride using an alkaline hydrogen peroxide solution using an organic underlayer film as an etching mask. In this case, the organic underlayer film also needs to be resistant to the alkaline hydrogen peroxide solution.
[0009] As described above, an organic lower layer film material for semiconductor device manufacturing is sought which has heat resistance of more than 300°C even in an oxygen-free inert gas, high filling / planarization characteristics, and adhesion to a substrate, and is highly suitable for wet etching treatment (i.e., resistance to alkaline hydrogen peroxide water), and a pattern forming method using the material.
[0010] Regarding a protective film having good alkaline hydrogen peroxide water resistance, Patent Document 1 and the like have been proposed. However, although this material has alkaline hydrogen peroxide water resistance, it has problems in terms of flattening performance on a high-height substrate and high heat resistance when a hard mask is formed on the protective film by CVD, ALD, etc., which are not satisfactory.
[0011] In addition, as for the examples having an imide structure shown in the present invention, there are known compounds having an imide structure described in Patent Documents 2 to 6, resins having a polyimide structure described in Patent Documents 7 to 9, and Patent Document 10 using a compound having a bismaleimide structure. There is no description related to the alkaline hydrogen peroxide water resistance of these materials, and the alkaline hydrogen peroxide water resistance of the resin having a polyimide structure is unknown.
[0012] Prior art literature
[0013] Patent Literature
[0014] [Patent Document 1] WO2017-191767
[0015] [Patent Document 2] WO2019-146378
[0016] [Patent Document 3] Japanese Patent Application Publication No. 2020-177225
[0017] [Patent Document 4] Japanese Patent Application Publication No. 2021-091841
[0018] [Patent Document 5] Japanese Patent Application Publication No. 2021-130763
[0019] [Patent Document 6] Japanese Patent Application Publication No. 2021-152639
[0020] [Patent Document 7] Japanese Patent Application Publication No. 2013-137334
[0021] [Patent Document 8] Japanese Patent Application Publication No. 2010-122297
[0022] [Patent Document 9] Japanese Patent Application Publication No. 2020-193325
[0023] [Patent Document 10] WO2018-212116 Summary of the invention
[0024] [Problems to be solved by the invention]
[0025] The present invention has been made in view of the above situation, and its object is to provide a protective film forming composition using a polymer containing an imide group, which can be hardened under film forming conditions not only in air but also in an inert gas, and can form a protective film that is not only excellent in heat resistance, but also in filling and planarizing characteristics of a pattern formed on a substrate and has good adhesion to the substrate, and can form a protective film with excellent alkaline hydrogen peroxide water resistance, and to provide a substrate for semiconductor device manufacturing, a protective film forming method, and a pattern forming method using the material.
[0026] [Methods for solving problems]
[0027] In order to solve the above problems, the present invention provides a protective film forming composition for alkaline hydrogen peroxide water.
[0028] Containing: (A) a polymer having fluorine atoms and hydroxyl groups represented by any one of the following (I) and (II), or a mixture of a polymer having fluorine atoms and a polymer having hydroxyl groups represented by the following (III), and (B) an organic solvent,
[0029] (I) A polymer having a repeating unit represented by the following general formula (1A) containing at least one fluorine atom and a hydroxyl group and having a terminal group represented by any one of the following general formulas (1B) and (1C),
[0030] (II) a polymer having a repeating unit containing at least one fluorine atom represented by the following general formula (2A) and a repeating unit containing at least one hydroxyl group represented by the following general formula (3A), and the terminal group is a group represented by any one of the following general formulas (1B) and (1C),
[0031] (III) a mixture of a polymer having a repeating unit containing at least one fluorine atom represented by the following general formula (2A) and having a terminal group represented by any one of the following general formulas (1B) and (1C), and a polymer having a repeating unit containing at least one hydroxyl group represented by the following general formula (3A) and having a terminal group represented by any one of the following general formulas (1B) and (1C),
[0032] [Chemistry 1]
[0033]
[0034] In the formula, W1 is one or more tetravalent organic groups which may also contain fluorine atoms or hydroxyl groups, W2 is one or more divalent organic groups which may also contain fluorine atoms or hydroxyl groups, and at least one of W1 and W2 contains one or more fluorine atoms, and at least one of W1 and W2 contains one or more hydroxyl groups.
[0035] [Chemistry 2]
[0036]
[0037] In the formula, W3 is one or more tetravalent organic groups which may contain fluorine atoms, W4 is one or more divalent organic groups which may contain fluorine atoms, and at least one of W3 and W4 contains one or more fluorine atoms.
[0038] [Chemistry 3]
[0039]
[0040] In the formula, W5 is one or more tetravalent organic groups which may contain a hydroxyl group, W6 is one or more divalent organic groups which may contain a hydroxyl group, and at least one of W5 and W6 contains one or more hydroxyl groups.
[0041] [Chemistry 4]
[0042]
[0043] [Chemistry 5]
[0044]
[0045] In the formula, R1 is any one of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.
[0046] [Chemistry 6]
[0047]
[0048] If such a protective film forming composition is used, the film forming conditions in the air and in the inert gas will harden due to the effect of the terminal cross-linking group. In addition, since the main chain is composed of a polyimide skeleton, a protective film that takes into account high heat resistance, good adhesion to the substrate, and high degree of embedding / planarization characteristics can be formed, and since there are fluorine atoms and hydroxyl groups in the polymer containing the imide group, it becomes a protective film forming composition that can form a protective film with excellent alkaline hydrogen peroxide water resistance. In addition, by using one or more W1 and W2, W3 and W4, or W5 and W6 as a combination of the above-mentioned organic groups, the thermal fluidity, heat resistance, and adhesion are better.
[0049] In addition, W2 in the general formula (1A) preferably contains at least one fluorine atom and a hydroxyl group.
[0050] It is preferable that the main chain has such a partial structure from the viewpoint of achieving both adhesion and excellent alkaline hydrogen peroxide water resistance.
[0051] In addition, W2 in the above general formula (1A) is preferably a group represented by the following general formula (1E).
[0052] [Chemistry 7]
[0053]
[0054] It is preferable that the main chain has such a partial structure from the viewpoint of heat resistance, flatness, adhesion, and further resistance to alkaline hydrogen peroxide water.
[0055] In addition, W1 in the above general formula (1A) is preferably any one of the groups represented by the following general formula (1F).
[0056] [Chemistry 8]
[0057]
[0058] It is preferable that the main chain has such a partial structure from the viewpoint of heat resistance and flatness, and further, resistance to alkaline hydrogen peroxide water.
[0059] It is further preferred to contain, as the component (A'), a polymer (IV) having a repeating unit represented by the following general formula (4A) and a terminal group represented by the following general formula (2C).
[0060] [Chemistry 9]
[0061]
[0062] In the formula, W7 is a tetravalent organic group, and W8 is a divalent organic group.
[0063] [Chemistry 10]
[0064]
[0065] In the formula, R2 represents a monovalent organic group having 1 to 10 carbon atoms, n1 represents an integer of 0 or 1, n2 and n3 are 1≤n2≤6 and 0≤n3≤6, and satisfy the relationship of 1≤n2+n3≤6.
[0066] It is preferable to contain a polymer (IV) having a hydroxyl group at the terminal group from the viewpoint of resistance to alkaline hydrogen peroxide water.
[0067] The weight average molecular weight of the component (A) is preferably 1,000 to 10,000.
[0068] When the protective film forming composition contains the polymer (A) within such a Mw range, the solubility in organic solvents is not impaired, and outgassing during baking can be suppressed.
[0069] The component (B) is preferably a mixture of one or more organic solvents having a boiling point of less than 180°C and one or more organic solvents having a boiling point of 180°C or higher.
[0070] According to such a protective film forming composition, thermal fluidity of the film can be imparted by adding a high-boiling-point solvent to the polymer (A), thereby achieving a protective film forming composition having both high-level filling and planarizing properties.
[0071] Furthermore, the protective film forming composition preferably further contains one or more of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer.
[0072] A protective film forming composition containing such a component can be a protective film forming composition having better coating properties and filling / planarization characteristics.
[0073] Furthermore, the protective film forming composition is preferably one that can provide a protective film that is resistant to hydrogen peroxide water containing ammonia.
[0074] Furthermore, the protective film forming composition is preferably such that when a silicon substrate having the protective film formed thereon is immersed in a 1.0 mass % hydrogen peroxide water containing 0.5 mass % ammonia at 70° C. for 5 minutes, no peeling of the protective film is observed.
[0075] Such a protective film forming composition has sufficient resistance to alkaline hydrogen peroxide water, so that options for processable substrates, silicon intermediate films that can be removed by wet etching, and the like can be increased.
[0076] The present invention also provides a substrate for manufacturing a semiconductor device, wherein a protective film formed by curing the protective film-forming composition is formed on the substrate.
[0077] If the protective film formed by curing the protective film forming composition of the present invention has both high filling and planarization characteristics, it will become a protective film without micro holes caused by poor filling and unevenness on the protective film surface caused by insufficient planarity. With such a protective film planarized substrate for semiconductor device manufacturing, the processing margin during patterning is widened, and semiconductor devices can be manufactured with good yield.
[0078] The present invention also provides a method for forming a protective film, which is a method for forming a protective film used in the manufacturing steps of a semiconductor device, wherein the protective film forming composition is spin-coated on a substrate to be processed, and the substrate to be processed coated with the protective film forming composition is heat-treated in an inert gas environment at a temperature in the range of 50° C. to 600° C. for 10 seconds to 7200 seconds to obtain a cured film.
[0079] The present invention also provides a method for forming a protective film, which is a method for forming a protective film used in the manufacturing steps of a semiconductor device, wherein the protective film forming composition is spin-coated on a substrate to be processed, the substrate to be processed coated with the protective film forming composition is heat-treated in air at a temperature of 50° C. to 250° C. for a period of 5 seconds to 600 seconds to form a coating film, and then heat-treated in an inert gas environment at a temperature of 200° C. to 600° C. for a period of 10 seconds to 7200 seconds to obtain a cured film.
[0080] The protective film used in the manufacturing steps of the semiconductor device formed by the method of the present invention has high heat resistance and high-level filling / planarization characteristics. If used in the manufacturing steps of the semiconductor device, the yield of the semiconductor device will become good.
[0081] At this time, the oxygen concentration in the inert gas is preferably 1% or less.
[0082] The protective film forming composition of the present invention can be sufficiently hardened without generating sublimates even when heated in such an inert gas atmosphere, and can form a protective film having excellent adhesion to the substrate.
[0083] Furthermore, it is preferred that the substrate to be processed has a structure with a height of 30 nm or more or a height difference.
[0084] The method for forming a protective film of the present invention is particularly useful for forming a flat protective film on such a substrate to be processed.
[0085] Furthermore, the present invention provides a pattern forming method, which is a method for forming a pattern on a processed substrate, comprising the following steps:
[0086] (I-1) forming a protective film on a substrate to be processed using the protective film forming composition,
[0087] (I-2) forming a silicon-containing resist intermediate film on the protective film using a silicon-containing resist intermediate film material,
[0088] (I-3) forming a resist upper layer film on the aforementioned silicon-containing resist intermediate film using a photoresist composition,
[0089] (I-4) forming a circuit pattern on the resist upper layer film,
[0090] (I-5) using the patterned resist upper film as a mask, transferring the pattern to the silicon-containing resist intermediate film by etching,
[0091] (I-6) using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask, transferring the pattern to the protective film by etching, and
[0092] (I-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0093] Furthermore, the present invention provides a pattern forming method, which is a method for forming a pattern on a processed substrate, comprising the following steps:
[0094] (II-1) forming a protective film on a substrate to be processed using the protective film forming composition,
[0095] (II-2) forming a silicon-containing resist interlayer film on the protective film using a silicon-containing resist interlayer film material,
[0096] (II-3) forming an organic antireflection film on the aforementioned silicon-containing resist intermediate film,
[0097] (II-4) forming a resist upper layer film on the organic antireflection film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film,
[0098] (II-5) using the patterned resist upper layer film as a mask, transferring the pattern to the organic anti-reflective film and the silicon-containing resist intermediate film by etching,
[0099] (II-6) using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask, transferring the pattern to the protective film by etching, and
[0100] (II-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0101] Furthermore, the present invention provides a pattern forming method, which is a method for forming a pattern on a processed substrate, comprising the following steps:
[0102] (III-1) forming a protective film on a substrate to be processed using the protective film forming composition,
[0103] (III-2) forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the protective film,
[0104] (III-3) forming a resist upper layer film on the inorganic hard mask using a photoresist composition,
[0105] (III-4) forming a circuit pattern on the resist upper layer film,
[0106] (III-5) using the patterned resist upper layer film as a mask, transferring the pattern to the inorganic hard mask film by etching,
[0107] (III-6) using the inorganic hard mask film to which the pattern has been transferred as a mask to etch and transfer the pattern to the protective film, and
[0108] (III-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0109] Furthermore, the present invention provides a pattern forming method, which is a method for forming a pattern on a processed substrate, comprising the following steps:
[0110] (IV-1) forming a protective film on a substrate to be processed using the protective film forming composition,
[0111] (IV-2) forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the protective film,
[0112] (IV-3) forming an organic antireflection film on the inorganic hard mask film,
[0113] (IV-4) forming a resist upper layer film on the organic antireflection film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film,
[0114] (IV-5) using the patterned resist upper layer film as a mask, transferring the pattern to the organic antireflective film and the inorganic hard mask by etching,
[0115] (IV-6) using the inorganic hard mask film to which the pattern has been transferred as a mask, and transferring the pattern to the protective film by etching, and
[0116] (IV-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0117] The protective film forming composition of the present invention can be preferably used in various pattern forming methods such as three-layer resist processing using a silicon-containing resist intermediate film or an inorganic hard mask, and four-layer resist processing using an organic anti-reflection film. In the manufacturing process of a semiconductor device, if a circuit pattern is formed by such a pattern forming method of the present invention, the semiconductor device can be manufactured with a good yield. In addition, as described above, the protective film formed using the protective film forming composition of the present invention has good alkaline hydrogen peroxide water resistance, so it can also be used in wet etching processing using alkaline hydrogen peroxide water.
[0118] Furthermore, the inorganic hard mask is preferably formed by a CVD method or an ALD method.
[0119] The pattern forming method of the present invention can form an inorganic hard mask in such a method, for example.
[0120] Furthermore, the present invention may be a pattern forming method which further comprises a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide solution after the step (I-6) or the step (II-6).
[0121] The protective film formed using the protective film forming composition of the present invention has good resistance to alkaline hydrogen peroxide water, so the silicon-containing resist intermediate film can be removed by wet etching using the alkaline hydrogen peroxide water as described above.
[0122] Furthermore, the present invention may be a pattern forming method having a step of transferring the pattern to the aforementioned processed substrate by using the protective film of the aforementioned transferred pattern as a mask and etching with alkaline hydrogen peroxide water in the aforementioned step (I-7), step (II-7), step (III-7), or step (IV-7).
[0123] The protective film formed using the protective film-forming composition of the present invention has excellent resistance to alkaline hydrogen peroxide water, and thus pattern transfer to a substrate to be processed can be performed by wet etching using the alkaline hydrogen peroxide water as described above.
[0124] Furthermore, the present invention may be a pattern forming method having a step of patterning the aforementioned processed substrate by using the protective film of the aforementioned transferred pattern as a mask and performing ion implantation in the aforementioned step (I-7), step (II-7), step (III-7), or step (IV-7).
[0125] Such a pattern forming method is particularly suitable for ion implantation processing of a substrate having an uneven surface.
[0126] At this time, after the step of patterning the substrate to be processed by ion implantation, there may be a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water.
[0127] The protective film formed using the protective film forming composition of the present invention has good resistance to alkaline hydrogen peroxide solution, and thus the silicon-containing resist intermediate film can be removed after patterning by ion implantation by wet etching using the alkaline hydrogen peroxide solution.
[0128] In forming the circuit pattern, it is preferred to form the circuit pattern by photolithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nano-stamping, or a combination thereof.
[0129] Furthermore, in the formation of the aforementioned circuit pattern, it is preferred that the circuit pattern be developed using an alkali developer or an organic solvent.
[0130] The pattern forming method of the present invention can preferably use such a circuit pattern forming means and developing means.
[0131] Furthermore, the aforementioned processed substrate is preferably a semiconductor device substrate, or a semiconductor device substrate on which any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film is formed.
[0132] At this time, the aforementioned processed substrate is preferably a substrate containing silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.
[0133] According to the pattern forming method of the present invention, the substrate to be processed can be processed to form a pattern as described above.
[0134] [Effects of the Invention]
[0135] As described above, the protective film forming composition of the present invention can form a hardened film without generating byproducts even when forming a film in a passive gas in which corrosion of the substrate is prevented, and is useful for forming a protective film having both high-level filling and planarization characteristics. In addition, the protective film forming composition of the present invention will become a material for forming a protective film having filling / planarization characteristics and having heat resistance, etching resistance, adhesion, alkaline hydrogen peroxide water resistance and other characteristics. Therefore, it is extremely useful as a protective film material in a multilayer resist method such as a two-layer resist method, a three-layer resist method using a silicon-containing intermediate film, and a four-layer resist method using a silicon-containing intermediate film and an organic anti-reflection film, or a planarization material for semiconductor device manufacturing. In addition, the protective film formed by the protective film forming composition of the present invention has excellent heat resistance, so even when a CVD hard mask is formed on the protective film, there is no change in film thickness due to thermal decomposition, and it is suitable for pattern formation. Furthermore, it is also extremely useful in a pattern forming method using wet etching processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0136] Figure 1 It is an explanatory diagram of the planarization characteristic of the present invention.
[0137] Figure 2 (A) to (F) are explanatory diagrams of an example of the pattern forming method using the three-layer resist method of the present invention.
[0138] Figure 3 (G) to (I) are explanatory diagrams of the landfill characteristic evaluation method of the embodiment.
[0139] Figure 4 (J) and (K) are explanatory diagrams of the planarization characteristic evaluation method of the embodiment. DETAILED DESCRIPTION
[0140] In order to prevent corrosion of the substrate, we seek to develop film forming conditions in a passive gas, for example: no by-products are generated even at temperatures above 300°C, and a protective film can be formed that not only has excellent filling and planarization properties for the pattern formed on the substrate, but also has good dry etching resistance during substrate processing. In addition, even when a CVD hard mask is formed on the protective film, the film thickness of the protective film does not change due to thermal decomposition, thereby forming a protective film-forming composition that has high suitability for wet etching processing (i.e., resistance to alkaline hydrogen peroxide water).
[0141] The inventors of the present application have made further efforts to study and found that by using the following polymers or polymer mixtures in the protective film forming composition, the protective film forming composition has the same thermal curing properties as the known lower film material not only in air but also in a passive gas, and has excellent thermal fluidity, so it has a high degree of filling / planarization characteristics:
[0142] A polymer having a main skeleton having a polyimide structure represented by the general formula (1A) containing at least one fluorine atom and a hydroxyl group and having introduced as an end group a group having a triple bond represented by the general formula (1B) or (1C) as a thermosetting group; a polymer having a main skeleton having a polyimide structure represented by the general formula (2A) containing at least one fluorine atom and a polyimide structure represented by the general formula (3A) containing at least one hydroxyl group and having introduced as an end group the general formulas (1B) or (1C); or a mixture of a polymer having a main skeleton having a polyimide structure represented by the general formula (2A) and having introduced as an end group the general formulas (1B) or (1C) and a polymer having a main skeleton having a polyimide structure represented by the general formula (3A) and having introduced as an end group the general formulas (1B) or (1C).
[0143] In addition, we have found that the protective film forming composition has high heat resistance without variation in coating film thickness due to thermal decomposition when forming a CVD hard mask, and good adhesion to the substrate. Furthermore, by studying the mixture of the polymers represented by (I) and (II) and the polymer represented by (III), we have found that a protective film forming composition having excellent alkaline hydrogen peroxide water resistance can be provided, and the present invention has been completed.
[0144] That is, the present invention is a protective film-forming composition for alkaline hydrogen peroxide water, which contains: (A) a polymer having fluorine atoms and hydroxyl groups represented by any one of the following (I) and (II), or a mixture of a polymer having fluorine atoms and a polymer having hydroxyl groups represented by the following (III), and (B) an organic solvent.
[0145] (I) A polymer having a repeating unit represented by the following general formula (1A) containing at least one fluorine atom and a hydroxyl group and having a terminal group represented by any one of the following general formulas (1B) and (1C),
[0146] (II) a polymer having a repeating unit containing at least one fluorine atom represented by the following general formula (2A) and a repeating unit containing at least one hydroxyl group represented by the following general formula (3A), and the terminal group is a group represented by any one of the following general formulas (1B) and (1C),
[0147] (III) a mixture of a polymer having a repeating unit containing at least one fluorine atom represented by the following general formula (2A) and having a terminal group represented by any one of the following general formulas (1B) and (1C), and a polymer having a repeating unit containing at least one hydroxyl group represented by the following general formula (3A) and having a terminal group represented by any one of the following general formulas (1B) and (1C),
[0148] [Chemistry 11]
[0149]
[0150] In the formula, W1 is one or more tetravalent organic groups which may also contain fluorine atoms or hydroxyl groups, W2 is one or more divalent organic groups which may also contain fluorine atoms or hydroxyl groups, and at least one of W1 and W2 contains one or more fluorine atoms, and at least one of W1 and W2 contains one or more hydroxyl groups.
[0151] [Chemistry 12]
[0152]
[0153] In the formula, W3 is one or more tetravalent organic groups which may contain fluorine atoms, W4 is one or more divalent organic groups which may contain fluorine atoms, and at least one of W3 and W4 contains one or more fluorine atoms.
[0154] [Chemistry 13]
[0155]
[0156] In the formula, W5 is one or more tetravalent organic groups which may contain a hydroxyl group, W6 is one or more divalent organic groups which may contain a hydroxyl group, and at least one of W5 and W6 contains one or more hydroxyl groups.
[0157] [Chemistry 14]
[0158]
[0159] [Chemistry 15]
[0160]
[0161] In the formula, R1 is any one of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.
[0162] [Chemistry 16]
[0163]
[0164] The present invention will be described in detail below, but the present invention is not limited to these.
[0165] <(A)Component>
[0166] The component (A) in the present invention is any one of the following polymers (I) and (II), or a mixture (III) of the polymers.
[0167] [Polymer (I)]
[0168] The protective film forming polymer used in the protective film forming composition of the present invention is a polymer (polymer (I)) having a repeating unit containing at least one fluorine atom and a hydroxyl group represented by the following general formula (1A) and the terminal group is a group represented by any one of the following general formulas (1B) and (1C).
[0169] [Chemistry 17]
[0170]
[0171] In the formula, W1 is one or more tetravalent organic groups which may also contain fluorine atoms or hydroxyl groups, W2 is one or more divalent organic groups which may also contain fluorine atoms or hydroxyl groups, and at least one of W1 and W2 contains one or more fluorine atoms, and at least one of W1 and W2 contains one or more hydroxyl groups.
[0172] [Chemistry 18]
[0173]
[0174] [Chemistry 19]
[0175]
[0176] In the formula, R1 is any one of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.
[0177] [Chemistry 20]
[0178]
[0179] By forming a pre-closed polyimide structure as described above (1A), (1B), and (1C), by-product dehydration and other separation reactions when the precursors of polyimide compounds such as polyamic acid are thermally closed will be eliminated, film shrinkage will be suppressed, and the flatness of the protective film will not be damaged. In addition, by forming a stable imide structure in advance, decomposition caused by the equilibrium reaction of polyimide compound precursors such as polyamic acid can be suppressed, which has advantages in terms of storage stability. In addition, the polyimide structure will impart heat resistance and help improve the adhesion to the substrate. Due to the improved adhesion, film peeling when an inorganic hard mask using the CVD method or the ALD method is formed directly on the protective film will be prevented, and a protective film with excellent processing margin can be formed. Furthermore, the presence of fluorine atoms and hydroxyl groups in the main skeleton of the polyimide structure represented by the above (1A) also helps to improve the resistance to alkaline hydrogen peroxide water. The effect of water repellency of the protective film against alkaline hydrogen peroxide water due to fluorine atoms and the effect of improving the adhesion between the protective film and the processed substrate due to hydroxyl groups are both obtained, so it is considered that peeling is suppressed in wet etching using alkaline hydrogen peroxide water, and as a result, good alkaline hydrogen peroxide water resistance is shown.
[0180] R1 represented by the above formula (1D) functions as a thermally crosslinkable group. From the viewpoints of curability, heat resistance, and availability of raw materials, ethynyl and ethynylphenyl are preferred.
[0181] W1 in the above general formula may be exemplified by the following structural formulas, and these aromatic rings may also have substituents. Further, the substituents may be exemplified by hydroxyl, trifluoromethyl, alkyl having 1 to 10 carbon atoms, alkynyl having 3 to 10 carbon atoms, alkenyl, alkoxy having 1 to 10 carbon atoms, alkynyloxy having 3 to 10 carbon atoms, alkenyloxy, aryl having 6 to 10 carbon atoms, nitro, halogen, nitrile, alkoxycarbonyl having 1 to 10 carbon atoms, alkanoyloxy having 1 to 10 carbon atoms, and the like.
[0182] [Chemistry 21]
[0183]
[0184] [Chemistry 22]
[0185]
[0186] [Chemistry 23]
[0187]
[0188] [Chemistry 24]
[0189]
[0190] [Chemistry 25]
[0191]
[0192] [Chemistry 26]
[0193]
[0194] W2 in the above general formula may include the following structural formulas, etc., and these aromatic rings may also have substituents. In addition, the substituents may include hydroxyl, trifluoromethyl, alkyl having 1 to 10 carbon atoms, alkynyl having 3 to 10 carbon atoms, alkenyl, alkoxy having 1 to 10 carbon atoms, alkynyloxy having 3 to 10 carbon atoms, alkenyloxy, aryl having 6 to 10 carbon atoms, thiol, nitro, halogen, nitrile, sulfonic acid, alkoxycarbonyl having 1 to 10 carbon atoms, alkanoyloxy having 1 to 10 carbon atoms, etc.
[0195] [Chemistry 27]
[0196]
[0197] [Chemistry 28]
[0198]
[0199] [Chemistry 29]
[0200]
[0201] [Chemistry 30]
[0202]
[0203] By making one or more W1 and W2 as a combination of organic groups as described above, thermal fluidity, heat resistance and adhesion can be improved. W1 and W2 can be one each, or a combination of two or more. However, considering the resistance to alkaline hydrogen peroxide water, the selected W1 and W2 must contain at least one fluorine atom and a hydroxyl group. That is, at least one of W1 and W2 contains one or more fluorine atoms, and at least one of W1 and W2 contains one or more hydroxyl groups.
[0204] In the polymer (I) used in the protective film forming composition of the present invention, W2 in the general formula (1A) preferably contains at least one fluorine atom and a hydroxyl group.
[0205] It is preferable that the main chain has such a partial structure from the viewpoint of achieving both adhesion and excellent alkaline hydrogen peroxide water resistance.
[0206] In the polymer (I) used in the protective film forming composition of the present invention, W2 in the aforementioned general formula (1A) is preferably a group represented by the following general formula (1E).
[0207] [Chemistry 31]
[0208]
[0209] The hexafluoroisopropyl group introduces bending properties into the main chain, which inhibits the aggregation of imide groups, and can take into account both high-level filling / planarization properties and heat resistance. Furthermore, the general formula (1E) has both a hexafluoroisopropyl group and a hydroxyl group, so the water repellency of the protective film against alkaline hydrogen peroxide water obtained by the hexafluoroisopropyl group and the effect of improving the adhesion between the protective film and the processed substrate obtained by the hydroxyl group can be effectively exerted, so it is more ideal from the perspective of alkaline hydrogen peroxide water resistance.
[0210] In the polymer used in the protective film forming composition of the present invention, W1 in the aforementioned general formula (1A) is preferably a group represented by the following general formula (1F).
[0211] [Chemistry 32]
[0212]
[0213] Since the hexafluoroisopropylidene group introduces bending properties into the main chain, it will inhibit the condensation of the imide groups, and can take into account a high degree of landfill / flattening properties and heat resistance. Furthermore, the hexafluoroisopropylidene group will improve the water repellency of alkaline hydrogen peroxide water, so it is also ideal to consider the resistance to alkaline hydrogen peroxide water. In addition, the linking group of the main chain is preferably a structure having a hexafluoroisopropylidene group and an ether bond. The ether bond acts as a soft linking group, which can impart thermal fluidity and solvent solubility, so it can take into account a higher degree of landfill / flattening properties and heat resistance.
[0214] The Mw (weight average molecular weight) of the polymer (I) is preferably 1000 to 10000, more preferably 1000 to 8000, and even more preferably 1500 to 5000. In the present invention, the weight average molecular weight may be a polystyrene-equivalent weight average molecular weight (Mw) obtained by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent.
[0215] If the molecular weight is such, the solubility in organic solvents can be ensured, and the sublimation products generated during baking can be suppressed. In addition, the thermal fluidity of the polymer of component (A) (polymer for forming a protective film) becomes good, and when it is mixed with the protective film forming composition, it can not only fill the fine structure formed on the substrate well, but also form a protective film that makes the entire substrate flat.
[0216] [Polymer (II)]
[0217] Furthermore, as a polymer having fluorine atoms and hydroxyl groups, (A) it may also be a polymer having a repeating unit containing at least one fluorine atom represented by the following general formula (2A) and a repeating unit containing at least one hydroxyl group represented by the following general formula (3A), and the terminal group is a group represented by any one of the following general formulas (1B) and (1C) (polymer (II)).
[0218] [Chemistry 33]
[0219]
[0220] In the formula, W3 is one or more tetravalent organic groups which may contain fluorine atoms, W4 is one or more divalent organic groups which may contain fluorine atoms, and at least one of W3 and W4 contains one or more fluorine atoms.
[0221] [Chemistry 34]
[0222]
[0223] In the formula, W5 is one or more tetravalent organic groups which may contain a hydroxyl group, W6 is one or more divalent organic groups which may contain a hydroxyl group, and at least one of W5 and W6 contains one or more hydroxyl groups.
[0224] [Chemistry 35]
[0225]
[0226] [Chemistry 36]
[0227]
[0228] In the formula, R1 is any one of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.
[0229] [Chemistry 37]
[0230]
[0231] The polymer (A) used in the present invention contributes to the improvement of alkaline hydrogen peroxide water resistance by the presence of fluorine atoms and hydroxyl groups in the main skeleton of the polyimide structure. Therefore, the polymer (A) is not limited to the polymer (I) having both fluorine atoms and hydroxyl groups in one repeating unit, but may also be a copolymer (polymer (II)) of repeating units having only fluorine atoms and repeating units having only hydroxyl groups. Like polymer (I), polymer (II) also provides good landfill / planarization characteristics, heat resistance, adhesion, and alkaline hydrogen peroxide water resistance.
[0232] In the repeating unit containing at least one fluorine atom represented by the general formula (2A), W3 is not particularly limited to being one or more tetravalent organic groups that may also contain fluorine atoms, for example, a specific example of W1 may be a group that does not contain a hydroxyl group among the above. W4 is not particularly limited to being one or more divalent organic groups that may also contain fluorine atoms, for example, a specific example of W2 may be a group that does not contain a hydroxyl group among the above. However, at least one of W3 and W4 contains one or more fluorine atoms.
[0233] In the repeating unit containing at least one hydroxyl group represented by the general formula (3A), W5 is one or more tetravalent organic groups which may also contain a hydroxyl group, and there is no particular limitation. For example, specific examples of W1 include groups which do not contain fluorine atoms among the above. W6 is one or more divalent organic groups which may also contain a hydroxyl group, and there is no particular limitation. For example, specific examples of W2 include groups which do not contain fluorine atoms among the above. However, at least one of W5 and W6 contains one or more hydroxyl groups.
[0234] The structure of the terminal group and the weight average molecular weight of the polymer (II) are the same as those described for the polymer (I).
[0235] [Polymer mixture (III)]
[0236] Furthermore, the component (A) of the present invention may be, in addition to being a copolymer (polymer (II)) of a repeating unit represented by the above general formula (2A) and a repeating unit represented by the above general formula (3A), a mixture (polymer mixture (III)) of a polymer having a repeating unit represented by the above general formula (2A) (polymer (III-1)) and a polymer having a repeating unit represented by the above general formula (3A) (polymer (III-2)).
[0237] Polymer (III-1) is a polymer having a repeating unit represented by the general formula (2A) containing at least one fluorine atom and a terminal group represented by any one of the general formulas (1B) and (1C). In polymer (III-1), the repeating unit represented by the general formula (2A), the structure of the terminal group represented by any one of the general formulas (1B) and (1C), and the weight average molecular weight are the same as those described for polymer (II).
[0238] Polymer (III-2) is a polymer having a repeating unit represented by the general formula (3A) containing at least one hydroxyl group and a terminal group represented by any one of the general formulas (1B) and (1C). In polymer (III-2), the repeating unit represented by the general formula (3A), the structure of the terminal group represented by any one of the general formulas (1B) and (1C), and the weight average molecular weight are the same as those described for polymer (II).
[0239] In the present invention, the fluorine atoms and hydroxyl groups in the main skeleton of the polyimide structure of component (A) are not necessarily contained in the same polymer. Even if the fluorine atoms in the main skeleton of the polyimide structure and the hydroxyl groups in the main skeleton of the polyimide structure are contained in separate polymers, the alkaline hydrogen peroxide water resistance can be improved. Therefore, like polymers (I) and (II), the polymer mixture (III) can also provide good filling / planarization characteristics, heat resistance, adhesion, and alkaline hydrogen peroxide water resistance.
[0240] [(A) Method for producing polymer]
[0241] The method for producing the polymer of the component (A) is described using the polymer (I) as an example, but the polymer (II), the polymer (III-1), and the polymer (III-2) can also be produced by the same method.
[0242] The means for obtaining the polymer used in the protective film forming composition of the present invention is to feed any of the following diamines and tetracarboxylic anhydrides in excess to obtain a polyamic acid intermediate having an amino group or a carboxylic anhydride active end (STEP1). After that, a polyimide precursor (STEP2) is synthesized from a phthalic anhydride derivative or an aniline derivative having R1 as a substituent as an end-capping agent, and then further thermally or chemically imidized (STEP3) is performed to synthesize the polymer of component (A). The diamine compound or tetracarboxylic anhydride used in the synthesis of the polyamic acid compound of STEP1, and the phthalic anhydride derivative or aniline derivative used for the end sealing of STEP2, can be used alone or in combination of two or more. They can be appropriately selected and combined according to the required characteristics. W1, W2, and R1 in the following formula are the same as those described above.
[0243] (Diamine excess condition)
[0244] [Chemistry 38]
[0245] STEP1
[0246]
[0247] [Chemistry 39]
[0248] STEP 2
[0249]
[0250] [Chemistry 40]
[0251] STEP 3
[0252]
[0253] (Tetracarboxylic acid excess condition)
[0254] [Chemistry 41]
[0255] STEP1
[0256]
[0257] [Chemistry 42]
[0258] STEP
[0259]
[0260] [Chemistry 43]
[0261] STEP 3
[0262]
[0263] The synthesis of the polyamic acid intermediate represented by STEP 1 can usually be carried out in an organic solvent at room temperature or under cooling or heating as needed. The solvent used may include alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, 1,4-dioxane, ethers such as dichloromethane, chloroform, dichloroethane, trichloroethylene, chlorine-based solvents such as hexane, heptane, benzene, toluene, xylene, cumene, etc. Hydrocarbons such as acetonitrile, nitriles such as acetonitrile, ketones such as acetone, ethyl methyl ketone, isobutyl methyl ketone, and cyclohexanone, esters such as methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol methyl ether acetate, and γ-butyrolactone, aprotic polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethylformamide, and hexamethylphosphoric triamide, and the like, and these can be used alone or in combination of two or more.
[0264] In the synthesis of these, a base catalyst may be used as necessary. Examples of the base catalyst include inorganic base compounds such as sodium bicarbonate, sodium carbonate, potassium carbonate, calcium carbonate, cesium carbonate, sodium hydroxide, potassium hydroxide, sodium hydride, potassium phosphate, and organic bases such as triethylamine, diisopropylethylamine, N,N-dimethylaniline, pyridine, and 4-dimethylaminopyridine. These may be used alone or in combination of two or more.
[0265] The reaction method includes a method of putting a diamine compound and a tetracarboxylic anhydride into a solvent in batches, a method of adding a diamine compound and a tetracarboxylic anhydride separately or mixed to disperse or dissolve them and then dropping them, and a method of dropping and putting one of the diamine compound and the tetracarboxylic anhydride dispersed or dissolved in a solvent. In addition, when there are multiple diamine compounds and tetracarboxylic anhydride feeds, a method of pre-mixing and reacting them can be adopted, and they can also be reacted in order. When a catalyst is used, a method of putting a diamine compound or a tetracarboxylic anhydride in batches, a method of dropping the catalyst after dispersing or dissolving the catalyst, etc. can be listed. The feed ratio of the diamine compound and the tetracarboxylic anhydride can be adjusted in an arbitrary ratio in a manner to form the desired Mw range. For example: when an aniline derivative is used as a capping agent for the next step, the tetracarboxylic anhydride can be used in excess for the diamine compound. When phthalic anhydride is used as a capping agent, a polyamide intermediate can be synthesized by using the diamine compound in excess relative to the tetracarboxylic anhydride. The obtained reaction solution of the polyamic acid intermediate can be used in the terminal sealing reaction of STEP 2, but in order to remove the unreacted raw materials, catalysts, etc. present in the system as reaction intermediates, it can also be diluted with an organic solvent, washed by liquid separation, and crystallized with a poor solvent to recover it in the form of powder.
[0266] The end sealing step of STEP2 is to react with the end-capping agent for the reaction solution of the above-mentioned polyamic acid intermediate (after pre-solubilization when recovered in powder form). The reaction solvent and reaction catalyst can use the same reaction solvent and reaction catalyst as the polyamic acid intermediate of STEP1. In addition, for the reaction method, except that the matrix does not use diamine compounds and tetracarboxylic anhydride but uses polyamic acid intermediate and aniline derivatives or phthalic anhydride as end-capping agents, it can be carried out in the same method as STEP1. The reaction solution of the obtained polyimide precursor can continue to be used in the imidization reaction of STEP3, but in order to remove the unreacted raw materials, catalysts, etc. present in the system as reaction intermediates, it can also be diluted with an organic solvent, washed by liquid separation, and crystallized by a poor solvent and recovered in powder form.
[0267] The imidization step shown in STEP 3 can be carried out by thermal or chemical imidization. These methods can be appropriately selected according to the thermal stability of the crosslinking group of the target imide compound and the reactivity of the introduced substituent with the reagent used in the chemical imidization.
[0268] When thermal imidization is carried out, a solvent that can azeotropize with water is added to the reaction solution of the polyamic acid obtained in STEP 2 (when recovered in powder form, it is pre-dissolved in a soluble solvent), heated to 100°C to 250°C, and a dehydration ring-closing reaction is carried out while removing the generated water to implement imidization.
[0269] Solvents that can be azeotroped with water include esters such as γ-butyrolactone, polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethylformamide, and non-polar solvents such as benzene, toluene, xylene, and mesitylene. It is better to heat these solvents alone or in mixture to distill the water generated by the closed loop to the outside of the system for dehydration.
[0270] In the case of chemical imidization, a base catalyst and an acid anhydride as a dehydrating agent are added to the reaction solution of the polyimide precursor obtained in step 2 (preliminarily dissolved in a soluble solvent when recovered in powder form) and heated to carry out imidization.
[0271] The base catalyst used in chemical imidization can be exemplified by pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. Among them, pyridine has a moderate alkalinity that allows the reaction to proceed, so it is ideal. The dehydrating agent can be exemplified by acetic anhydride, trimellitic anhydride, pyromellitic anhydride, trifluoroacetic anhydride, polyphosphoric acid, phosphorus pentoxide, phosphorus pentachloride, thionyl chloride, etc., and acetic anhydride is preferred from the perspective of purification after the reaction. In addition, the base catalyst and the dehydrating agent can be used separately, alone or in combination of two or more, and they can be used in accordance with the required performance of the target compound, and the catalyst amount, dehydrating amount, reaction temperature, and reaction time can be adjusted to appropriately control the imidization rate.
[0272] The solvent used at this time is not particularly limited as long as it is a solvent inactive in the above reaction. For example, ethers such as diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane, chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene, hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene, nitriles such as acetonitrile, ketones such as acetone, ethyl methyl ketone, isobutyl methyl ketone, and cyclohexanone, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol methyl ether acetate, γ-butyrolactone and other esters, N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethylformamide, hexamethylphosphoric triamide and other aprotic polar solvents, etc., can be used alone or in combination.
[0273] After the reaction is completed, the composition can be used directly as a protective film-forming composition, or it can be diluted with an organic solvent to remove unreacted raw materials, catalysts, etc. present in the system, and then separated, washed, and recovered.
[0274] The organic solvent used for liquid separation and cleaning is not particularly limited as long as it can dissolve the compound and separate into two layers when mixed with water. Examples include hydrocarbons such as hexane, heptane, benzene, toluene, and xylene, esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate, ketones such as methyl ethyl ketone, methyl amyl ketone, cyclohexanone, and methyl isobutyl ketone, ethers such as diethyl ether, diisopropyl ether, methyl-tert-butyl ether, and ethyl cyclopentyl methyl ether, chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene, and mixtures thereof. The cleaning water used at this time can be water commonly known as deionized water or ultrapure water. The number of cleaning times can be more than one, and even if it is washed more than 10 times, the corresponding cleaning effect may not be obtained, so it is preferably about 1 to 5 times.
[0275] In order to remove unreacted raw materials or acidic components in the system during separation and washing, an alkaline aqueous solution can also be used for washing. Specifically, the base includes, for example, alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, ammonia, and organic ammonium.
[0276] Furthermore, in order to remove unreacted raw materials, metal impurities or alkaline components in the system during separation and washing, an acidic aqueous solution can also be used for washing. Specifically, the acid includes inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropoly acids, and organic acids such as oxalic acid, fumaric acid, maleic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid.
[0277] The liquid separation washing with the alkaline aqueous solution and the acidic aqueous solution may be performed alone or in combination. Liquid separation washing with the alkaline aqueous solution and the acidic aqueous solution in this order is preferred from the viewpoint of removing metal impurities.
[0278] After the above-mentioned separation and cleaning using alkaline aqueous solution and acidic aqueous solution, it can also be cleaned with neutral water. The number of cleaning times can be more than 1 time, preferably about 1 to 5 times. Neutral water can be deionized water, ultrapure water, etc. described above. The number of cleaning times can be more than 1 time, but sometimes the alkaline component and acidic component cannot be removed when the number of times is small. Even if washing more than 10 times, the corresponding cleaning effect may not be obtained, so it is preferably about 1 to 5 times.
[0279] In addition, the reaction product after the liquid separation operation can be recovered in the form of powder by concentrating the solvent to dryness or crystallizing under reduced pressure or normal pressure, but in order to improve the operability when preparing the protective film forming composition, it can also be made into a solution state of appropriate concentration. At this time, the concentration is preferably 0.1 to 50% by mass, and more preferably 0.5 to 30% by mass. If it is such a concentration, the viscosity is not easy to increase, which can prevent the operability from being damaged. In addition, the amount of solvent will not become too large, so it is economical.
[0280] The solvent in this case is not particularly limited as long as it can dissolve the reaction product (polymer of component (A)). Specific examples include ketones such as cyclohexanone and methyl-2-pentanone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; and esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, t-butyl acetate, t-butyl propionate, and propylene glycol mono-t-butyl ether acetate. These may be used alone or in combination of two or more.
[0281] When synthesizing the above-mentioned polyimide, the diamine compound constituting the main chain of the polymer, the tetracarboxylic anhydride derivative, the phthalic acid derivative used for the end sealing, and the aniline derivative can be combined according to the required performance. Specifically, substituents that contribute to the improvement of solvent solubility, adhesion, and embedding / planarization characteristics, substituents that contribute to etching resistance and film forming properties, and substituents that contribute to alkaline hydrogen peroxide water resistance can be introduced according to the desired required performance. The protective film forming composition using these polymers can take into account embedding / planarization characteristics and heat resistance and alkaline hydrogen peroxide water resistance in a high dimension.
[0282] As described above, the polymer of the component (A) can provide a protective film forming composition that has heat resistance of 400° C. or higher, high-level filling / planarization characteristics, and alkaline hydrogen peroxide water resistance.
[0283] In the present invention, the flattening property is the property of flattening the surface of the substrate. Figure 1As shown, a protective film forming composition 3' is coated on the substrate 1, and the protective film 3 is formed by heating, thereby reducing the height difference of the substrate 1 from 100nm to less than 30nm. Figure 1 The height difference shape shown is a typical example of the height difference shape of a substrate used for manufacturing a semiconductor device. The height difference shape of a substrate that can be planarized by the protective film forming composition of the present invention is of course not limited to this.
[0284] <Protective Film Forming Composition>
[0285] The present invention provides a protective film-forming composition for alkaline hydrogen peroxide solution, which comprises (A) the above-mentioned polymer or a mixture of polymers, and (B) an organic solvent. In the protective film-forming composition of the present invention, the above-mentioned component (A) can be used alone or in combination of two or more.
[0286] The organic solvent that can be used in the protective film forming composition of the present invention is not particularly limited as long as it can dissolve the constituent components contained in the above-mentioned base polymer and the acid generator, cross-linking agent, other additives and other materials described later. Specifically, solvents with a boiling point of less than 180°C, such as the solvents described in paragraphs (0091) to (0092) of Japanese Patent Gazette No. 2007-199653, can be used. Among them, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, 2-heptanone, cyclopentanone, cyclohexanone and a mixture of two or more of these are more ideal. The amount of the organic solvent blended is preferably 200 to 10,000 parts by mass, and more preferably 300 to 5,000 parts by mass relative to 100 parts by mass of component (A).
[0287] Such a protective film forming composition can be applied by spin coating and contains the above-mentioned component (A), so it can be a protective film forming composition that has heat resistance of 400° C. or more, high filling / planarization characteristics, and alkaline hydrogen peroxide water resistance.
[0288] Furthermore, in the protective film forming composition of the present invention, a high boiling point solvent (a mixture of a solvent having a boiling point of less than 180°C and a solvent having a boiling point of more than 180°C) may be added to the above-mentioned solvent having a boiling point of less than 180°C as an organic solvent. The high boiling point organic solvent may be any solvent capable of dissolving component (A), and may be any hydrocarbon, alcohol, ketone, ester, ether, chlorine-based solvent, etc. Specific examples thereof include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-hexanediol, diethylene glycol. , dipropylene glycol, triethylene glycol, tripropylene glycol, glycerol, n-nonyl acetate, ethylene glycol monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol monomethyl ether, Triethylene glycol n-butyl ether, triethylene glycol butyl methyl ether, triethylene glycol diacetate, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetin, propylene glycol di Acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol methyl n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butanediol diacetate, 1,6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, dibutyl adipate, etc., which can be used alone or in combination.
[0289] The boiling point of the high boiling point solvent can be appropriately selected in accordance with the temperature at which the protective film forming composition is heat treated. The boiling point of the added high boiling point solvent is preferably 180°C to 300°C, and more preferably 200°C to 300°C. If the boiling point is such, there is no risk of excessive volatilization during baking (heat treatment) due to the boiling point being too low, and sufficient thermal fluidity can be obtained. In addition, if the boiling point is such, there is no risk of the solvent remaining in the film even after baking due to the high boiling point, so there is no risk of adversely affecting the film properties such as etching resistance.
[0290] When the high boiling point solvent is used, the blending amount of the high boiling point solvent is preferably 1 to 30 parts by mass relative to 100 parts by mass of the solvent having a boiling point of less than 180° C. If the blending amount is such, there is no risk that the blending amount is too small and sufficient thermal fluidity cannot be imparted during baking, or that the blending amount is too large and remains in the film, causing the film physical properties such as etching resistance to deteriorate.
[0291] In such a protective film forming composition, by adding a high boiling point solvent to the above-mentioned component (A) to impart thermal fluidity, the protective film forming composition can achieve both higher filling and planarizing properties.
[0292] <(A')Component>
[0293] [Polymer (IV)]
[0294] The protective film-forming composition of the present invention may contain, in addition to the above-mentioned component (A), a polymer (IV) having a repeating unit represented by the following general formula (4A) and a terminal group represented by the following general formula (2C) as the component (A').
[0295] [Chemistry 44]
[0296]
[0297] In the formula, W7 is a tetravalent organic group, and W8 is a divalent organic group.
[0298] [Chemistry 45]
[0299]
[0300] In the formula, R2 represents a monovalent organic group having 1 to 10 carbon atoms, n1 represents an integer of 0 or 1, and n2 and n3 are 1≤n2≤6 and 0≤n3≤6 and satisfy the relationship of 1≤n2+n3≤6.
[0301] The amount of polymer (IV) is preferably 1 to 30 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of component (A). Such an amount does not deteriorate heat resistance, but improves adhesion to the substrate by utilizing the terminal hydroxyl groups and improves resistance to alkaline hydrogen peroxide solution.
[0302] The substituent represented by OR2 can be appropriately selected according to the intended use, such as an alkoxy group for imparting fluidity, an alkenyl group for imparting curability under an inert gas, an alkynyloxy group, etc. By having a substituent represented by OR2, appropriate solvent solubility can be exhibited, and excellent solvent resistance and heat resistance can be exhibited after curing.
[0303] The Mw (weight average molecular weight) of the polymer (IV) is preferably 1000 to 10000, more preferably 1000 to 8000, and even more preferably 1500 to 5000. In the present invention, the weight average molecular weight may be a polystyrene-equivalent weight average molecular weight (Mw) obtained by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent.
[0304] In the above general formula (4A), specific examples of W7 are the same as the specific examples of W1 mentioned above.
[0305] In the above general formula (4A), specific examples of W8 are the same as the specific examples of W2 mentioned above.
[0306] Examples of the terminal group represented by the general formula (2C) include the following structural formulas.
[0307] [Chemistry 46]
[0308]
[0309] The polymer (IV) can also be produced by the same method as the method for producing the polymer (A) described above.
[0310] In order to further promote the curing reaction, (C) an acid generator may be added to the protective film forming composition of the present invention. Acid generators include acid generators that generate acid by thermal decomposition and acid generators that generate acid by light irradiation, and both can be added. Specifically, materials described in paragraphs (0061) to (0085) of Japanese Patent Publication No. 2007-199653 may be added, but are not limited to these.
[0311] The acid generators may be used alone or in combination of two or more. The amount of the acid generator added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, based on 100 parts of the component (A).
[0312] In order to improve the coating properties of spin coating, a (D) surfactant may be added to the protective film forming composition of the present invention. The surfactant may be, for example, the surfactants described in (0142) to (0147) in Japanese Patent Application Publication No. 2009-269953. The amount of the surfactant added is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the component (A).
[0313] Furthermore, in the protective film forming composition of the present invention, in order to improve the hardening property and further suppress the cross-mixing with the upper film, (E) a crosslinking agent may also be added. The crosslinking agent is not particularly limited, and various well-known crosslinking agents can be widely used. For example, melamine crosslinking agents, glycoluril crosslinking agents, benzoguanamine crosslinking agents, urea crosslinking agents, β-hydroxyalkylamide crosslinking agents, isocyanurate crosslinking agents, aziridine crosslinking agents, oxazoline crosslinking agents, and epoxy crosslinking agents can be cited.
[0314] Specifically, melamine-based crosslinking agents include hexamethoxymethylated melamine, hexabutoxymethylated melamine, these alkoxy and / or hydroxyl substitutions, and partial self-condensation products of these. Specifically, glycoluril-based crosslinking agents include tetramethoxymethylated glycoluril, tetrabutoxymethylated glycoluril, these alkoxy and / or hydroxyl substitutions, and partial self-condensation products of these. Specifically, benzoguanamine-based crosslinking agents include tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, these alkoxy and / or hydroxyl substitutions, and partial self-condensation products of these. Specifically, urea-based crosslinking agents include dimethoxymethylated dimethoxyethylene urea, its alkoxy and / or hydroxyl substitutions, and partial self-condensation products of these. Specifically, β-hydroxyalkylamide-based crosslinking agents include N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide. Specific examples of the isocyanurate crosslinking agent include triglycidyl isocyanurate and triallyl isocyanurate. Specific examples of the aziridine crosslinking agent include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate]. Specific examples of the oxazoline crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis-4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tert-butyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymers. Specific examples of epoxy crosslinking agents include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butylene glycol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether. The amount of the crosslinking agent added is preferably 1 to 100 parts by mass, more preferably 5 to 50 parts by mass, relative to 100 parts by mass of the component (A).
[0315] In addition, in order to make the planarization / burying characteristics better, a (F) plasticizer can be added to the protective film forming composition of the present invention. There is no particular limitation on the plasticizer, and plasticizers of various known systems can be widely used. For example, low molecular weight compounds such as phthalates, adipic acid esters, phosphates, trimellitic acid esters, and citrates, polyethers, polyesters, and polymers such as polyacetal polymers described in Japanese Patent Application Laid-Open No. 2013-253227 can be listed. When adding the plasticizer, the addition amount is preferably 1 to 100 parts by mass, and more preferably 5 to 50 parts by mass, relative to 100 parts by mass of component (A).
[0316] Furthermore, in the protective film forming composition of the present invention, as an additive for imparting the same filling / planarizing properties as the plasticizer, for example, a liquid additive having a polyethylene glycol or polypropylene glycol structure, or a thermally decomposable polymer having a weight loss rate of 40% by mass or more between 30°C and 250°C and a weight average molecular weight of 300 to 200,000 is preferred. The thermally decomposable polymer preferably contains a repeating unit having an acetal structure represented by the following general formula (DP1) or (DP1a). The amount of the liquid additive or thermally decomposable polymer added is preferably 1 to 100 parts by mass, more preferably 5 to 50 parts by mass, relative to 100 parts by mass of component (A).
[0317] [Chemistry 47]
[0318]
[0319] In the formula, R6 is a hydrogen atom or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms. Y1 is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.
[0320] [Chemistry 48]
[0321]
[0322] In the formula, R 6a Y is an alkyl group having 1 to 4 carbon atoms. a It is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, and may have an ether bond. n represents the average number of repeating units, and is 3 to 500.
[0323] Furthermore, the protective film forming composition of the present invention is preferably a protective film forming composition that provides a protective film that is resistant to hydrogen peroxide water containing ammonia. If such a protective film forming composition is used, a protective film having good resistance to alkaline hydrogen peroxide water can be formed, so it can also be used in wet etching treatment using alkaline hydrogen peroxide water.
[0324] Alkaline hydrogen peroxide is generally used for cleaning semiconductor wafers. In particular, a mixture of 5 parts by mass of deionized water, 1 part by mass of 29% ammonia water, and 1 part by mass of 30% hydrogen peroxide is called SC1 (Standard Clean-1), which is a standard solution for cleaning and removing organic impurities and particles on the surface of the wafer. In addition, alkaline hydrogen peroxide can be used to strip or etch a portion of metals and metal compounds, and also silicon-containing resist intermediate films designed for wet stripping. The composition of the alkaline hydrogen peroxide used in these processes is not particularly limited, and generally speaking, it is a mixture of deionized water, hydrogen peroxide, and ammonia. At this time, the concentration of hydrogen peroxide is preferably 0.1 to 10% by mass, and more preferably 0.2 to 5% by mass, and the concentration of ammonia is preferably 0.1 to 10% by mass, and more preferably 0.2 to 5% by mass. The processing temperature is preferably 0 to 90°C, and more preferably 20 to 80°C.
[0325] Here, the alkaline hydrogen peroxide water resistance test of the protective film is described. First, on a silicon wafer cut into 3 cm squares, a protective film forming composition is formed into a film with a thickness of about 100 nm according to the film forming conditions described below. The wafer is immersed in 1.0 mass% hydrogen peroxide water containing 0.5 mass% ammonia at 70°C for 5 minutes, and then rinsed with deionized water. It can be visually checked whether the protective film has peeled off from the wafer. When part or all of the protective film is peeled off and the surface of the silicon wafer is exposed, it is judged that the alkaline hydrogen peroxide water resistance of the protective film to be tested is insufficient.
[0326] That is, when the protective film formed by the protective film forming composition of the present invention is immersed in 1.0 mass % hydrogen peroxide water containing 0.5 mass % ammonia at 70° C. for 5 minutes, it is preferred that no peeling of the protective film is observed.
[0327] As described above, if it is the protective film forming composition of the present invention, it will become a protective film forming composition that takes into account heat resistance above 400°C, high-level filling / planarization characteristics, and alkaline hydrogen peroxide water resistance. Therefore, the protective film forming composition of the present invention is very useful as a protective film forming composition for multi-layer resist methods such as a two-layer resist method, a three-layer resist method using a silicon-containing resist intermediate film or a silicon-containing inorganic hard mask, and a four-layer resist method using a silicon-containing resist intermediate film or a silicon-containing inorganic hard mask and an organic anti-reflection film. In addition, the protective film forming composition of the present invention does not produce by-products even when forming a film in a passive gas, and has excellent filling / planarization characteristics, so it is also ideal as a planarization material for semiconductor device manufacturing steps other than the multi-layer resist method. Furthermore, it is also very useful in a pattern forming method using a wet etching process.
[0328] <Substrate for semiconductor device manufacturing>
[0329] The present invention also provides a substrate for manufacturing a semiconductor device, wherein a protective film formed by curing the protective film-forming composition is formed on the substrate.
[0330] If the protective film formed by hardening the protective film forming composition of the present invention, by taking into account the high degree of filling / flattening characteristics, it will become a protective film without micro-voids caused by poor filling and unevenness on the protective film surface caused by insufficient flatness. The substrate for semiconductor device manufacturing flattened with such a protective film has a wide processing margin during patterning, and semiconductor devices can be manufactured with a good yield. Furthermore, it becomes a protective film with alkaline hydrogen peroxide water resistance, so it also has high suitability for wet etching processing.
[0331] <Protective Film Formation Method>
[0332] The heating film forming step for forming the protective film can adopt one-stage baking, two-stage baking or three or more-stage baking, but one-stage baking or two-stage baking is more ideal in terms of economy. Film formation using one-stage baking is carried out, for example, at a temperature of 100°C to 600°C for 5 to 3600 seconds, but it is preferably carried out at a temperature of 150°C to 500°C for 10 to 7200 seconds. By heat treating under such conditions, flattening and cross-linking reactions using heat flow can be promoted. In the multilayer resist method, a coated silicon intermediate film and a CVD hard mask are sometimes formed on the obtained film. When a coated silicon intermediate film is used, it is better to form the film at a temperature higher than the temperature at which the silicon intermediate film is formed. Usually, the silicon intermediate film is formed at a temperature of 100°C to 400°C, preferably at a temperature of 150°C to 350°C. If the protective film is formed at a temperature higher than this temperature, it is possible to prevent the protective film from being dissolved by the composition for forming the silicon intermediate film, and to form a protective film that is not mixed with the composition.
[0333] When a CVD hard mask is used, it is preferred that the protective film be formed at a higher temperature than the temperature at which the CVD hard mask is formed. The temperature at which the CVD hard mask is formed is, for example, 150° C. to 500° C.
[0334] On the other hand, in the film formation by two-stage baking, if the influence of substrate corrosion caused by oxygen in the air is taken into consideration, the upper limit of the processing temperature in the air is, for example, below 300°C, preferably below 250°C, and within the range of 10 to 600 seconds. The baking temperature of the second stage is preferably higher than the baking temperature of the first stage but below 600°C, preferably below 500°C, and within the range of 10 to 7200 seconds. In the multilayer resist method, a coating type silicon intermediate film and a CVD hard mask are sometimes formed on the film obtained. When a coating type silicon intermediate film is used, it is preferable to form the film at a higher temperature than the temperature at which the silicon intermediate film is formed. Usually, the silicon intermediate film is formed at a temperature of 100°C to 400°C, preferably 150°C to 350°C. If the protective film is formed at a temperature higher than this temperature, the dissolution of the protective film due to the silicon intermediate film forming composition can be prevented, and a protective film that does not mix with the composition can be formed.
[0335] When a CVD hard mask is used in the two-step baking, it is preferred that the protective film be formed at a temperature higher than the temperature at which the CVD hard mask is formed. The temperature at which the CVD hard mask is formed may be 150°C to 500°C.
[0336] The present invention also provides a method for forming a protective film used in a manufacturing step of a semiconductor device. In order to prevent corrosion of a substrate being processed, the substrate being processed is heat treated in a gas environment with an oxygen concentration of less than 1% to form a hardened film.
[0337] This protective film forming method, for example, first spin-coats the protective film forming composition of the present invention onto the substrate to be processed. After spin-coating, in a two-stage baking, first bake in air at a temperature below 300°C, and then perform a second-stage baking in a gas environment with an oxygen concentration of less than 1%. During the first-stage baking, the first-stage baking in air can be skipped. In addition, the gas environment during baking can include inert gases such as nitrogen, argon, and helium. If it is the protective film forming composition of the present invention, even if it is calcined in such an inert gas environment, no sublimates are produced and a fully hardened protective film is formed.
[0338] In addition, the protective film forming method of the present invention can be used for a substrate to be processed that has a structure or a height difference of 30 nm or more. As described above, the protective film forming composition of the present invention has excellent filling / flattening properties, so even if the substrate to be processed has a structure or a height difference (concave and convex) of 30 nm or more, a flat hardened film can still be formed. That is, the protective film forming method of the present invention is particularly useful for forming a flat protective film on such a substrate to be processed.
[0339] The thickness of the protective film formed can be appropriately selected, and is preferably 30 to 20,000 nm, and more preferably 50 to 15,000 nm.
[0340] Furthermore, the above-mentioned method for forming a protective film can be applied to both the case of forming a protective film for pattern formation and the case of forming a protective film for a planarization film using the protective film forming composition of the present invention.
[0341] The present invention provides a method for forming a protective film, which is a method for forming a protective film used in the manufacturing steps of a semiconductor device. The protective film forming composition is spin-coated on a processed substrate, and the processed substrate coated with the protective film forming composition is subjected to heat treatment in an inert gas environment at a temperature in the range of 50°C to 600°C for 10 seconds to 7200 seconds to obtain a hardened film.
[0342] The present invention also provides a method for forming a protective film, which is a method for forming a protective film used in the manufacturing steps of a semiconductor device, wherein the protective film forming composition is spin-coated on a substrate to be processed, the substrate to be processed coated with the protective film forming composition is heat-treated in air at a temperature of 50°C to 250°C for 5 seconds to 600 seconds, preferably 10 seconds to 600 seconds to form a coating film, and then heat-treated in an inert gas environment at a temperature of 200°C to 600°C, preferably 250°C or more, for 10 seconds to 7200 seconds to obtain a cured film.
[0343] The protective film used in the manufacturing steps of the semiconductor device formed by the method of the present invention has high heat resistance and high-level filling / planarization characteristics. If used in the manufacturing steps of the semiconductor device, the yield of the semiconductor device becomes good.
[0344] The protective film forming method firstly spin-coats (spins) the protective film forming composition of the present invention onto the substrate to be processed. By using the spin coating method, good filling characteristics can be obtained. After spin coating, baking (heat treatment) is performed to promote flattening and cross-linking reactions by heat flow. In addition, by this baking, the solvent in the protective film forming composition can be evaporated, so that mixing can be prevented when the resist upper film and the silicon-containing resist intermediate film are formed on the protective film.
[0345] <Pattern Formation Method>
[0346] [Three-layer resist method using a silicon-containing resist interlayer]
[0347] Furthermore, the present invention provides a pattern forming method, which is a method for forming a pattern on a processed substrate, comprising the following steps:
[0348] (I-1) forming a protective film on a substrate to be processed using the protective film forming composition,
[0349] (I-2) forming a silicon-containing resist intermediate film on the protective film using a silicon-containing resist intermediate film material,
[0350] (I-3) forming a resist upper layer film on the aforementioned silicon-containing resist intermediate film using a photoresist composition,
[0351] (I-4) forming a circuit pattern on the resist upper layer film,
[0352] (I-5) using the patterned resist upper film as a mask, transferring the pattern to the silicon-containing resist intermediate film by etching,
[0353] (I-6) using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask, transferring the pattern to the protective film by etching, and
[0354] (I-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0355] The processed substrate is preferably a semiconductor device substrate, or a substrate on which a metal film, metal carbide film, metal oxide film, metal nitride film, metal oxide carbide film, and metal oxide nitride film are formed. More specifically, without particular limitation, Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al and other substrates, as well as substrates on which the above-mentioned metal films as the processed layer have been formed, can be used.
[0356] The processed layer can be made of various low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si and their barrier films, and can usually be formed with a thickness of 50 to 10,000 nm, especially 100 to 5,000 nm. In addition, when forming the processed layer, the substrate and the processed layer are made of different materials.
[0357] In addition, the metal constituting the processed substrate is preferably silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.
[0358] Furthermore, it is preferred that the substrate to be processed has a structure with a height of 30 nm or more or a height difference.
[0359] When forming a protective film on a substrate to be processed using the protective film-forming composition of the present invention, the protective film-forming method of the present invention described above can be used.
[0360] Then, a resist interlayer film (silicon-containing resist interlayer film) is formed on the protective film using a resist interlayer film material containing silicon atoms. The silicon-containing resist interlayer film material is preferably a polysiloxane-based interlayer film material. The silicon-containing resist interlayer film can suppress reflection by having an anti-reflection effect. In particular, for 193nm exposure, if a material containing a large amount of aromatic groups and having a high etching selectivity with the substrate is used as a protective film forming composition, the k value is high and the substrate reflection is increased, but by making it have an absorption with a suitable k value for the silicon-containing resist interlayer film, the reflection can be suppressed and the substrate reflection can be made less than 0.5%. As a silicon-containing resist interlayer film with an anti-reflection effect, for 248nm and 157nm exposure, a polysiloxane having anthracene and cross-linked by acid or heat can be preferably used, and for 193nm exposure, a polysiloxane having a light-absorbing group having a phenyl group or a silicon-silicon bond and cross-linked by acid or heat can be preferably used.
[0361] Then, a resist upper film is formed on the silicon-containing resist intermediate film using a resist upper film material composed of a photoresist composition. The resist upper film material can be either positive or negative, and can be the same material as the commonly used photoresist composition. After the resist upper film material is spin-coated, it is preferably pre-baked at 60 to 180° C. for 10 to 300 seconds. Thereafter, exposure is performed according to the usual method, and then post-exposure baking (PEB) and development are performed to obtain a resist upper film pattern. In addition, there is no special restriction on the thickness of the resist upper film, 30 to 500 nm is ideal, and 50 to 400 nm is particularly preferred.
[0362] Then, a circuit pattern (resist upper film pattern) is formed on the resist upper film. The circuit pattern is preferably formed by photolithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nano-stamping, or a combination thereof.
[0363] In addition, the exposure light is a high-energy ray with a wavelength of less than 300nm, specifically, far ultraviolet light, KrF excimer laser (248nm), ArF excimer laser (193nm), F2 laser (157nm), Kr2 laser (146nm), Ar2 laser (126nm), 3 to 20nm soft X-ray (EUV), electron beam (EB), ion beam, X-ray, etc.
[0364] In the formation of the circuit pattern, it is preferred to develop the circuit pattern using an alkali developer or an organic solvent.
[0365] Then, the resist upper film on which the circuit pattern has been formed is used as a mask to transfer the pattern to the silicon-containing resist intermediate film by etching. The etching of the silicon-containing resist intermediate film using the resist upper film pattern as a mask is preferably performed using a fluorocarbon-based gas. Thus, a silicon-containing resist intermediate film pattern is formed.
[0366] Then, the pattern is transferred to the organic film by etching using the silicon-containing resist interlayer film with the transferred pattern as a mask. Compared with organic matter, the silicon-containing resist interlayer film has a higher etching resistance to oxygen or hydrogen, so the etching of the protective film using the silicon-containing resist interlayer film pattern as a mask is preferably performed using an etching gas mainly composed of oxygen or hydrogen. In this way, a protective film pattern is formed.
[0367] Then, the protective film with the transferred pattern is used as a mask to form a pattern on the processed substrate by etching. For example, the protective film with the transferred pattern is used as a mask to transfer the pattern to the processed substrate by etching. The etching of the processed body (processed layer) can be carried out according to the usual method. For example, if the processed body is SiO2, SiN, or a silicon dioxide-based low dielectric constant insulating film, etching is mainly carried out using a fluorine-based gas. If it is p-Si, Al, or W, etching is mainly carried out using a chlorine-based or bromine-based gas. When etching is performed with a fluorine-based gas during substrate processing, the silicon-containing resist intermediate film pattern will be stripped off at the same time as the substrate processing. On the other hand, when etching is performed with a chlorine-based or bromine-based gas during substrate processing, in order to strip off the silicon-containing resist intermediate film pattern, dry etching stripping using a fluorine-based gas must be performed after the substrate processing.
[0368] As described above, the protective film obtained by using the protective film-forming composition of the present invention has excellent etching resistance when the substrate to be processed is etched.
[0369] [Four-layer resist method using silicon-containing resist interlayer and organic antireflection film]
[0370] Furthermore, the present invention provides a pattern forming method, which is a method for forming a pattern on a processed substrate, comprising the following steps:
[0371] (II-1) forming a protective film on a substrate to be processed using the protective film forming composition,
[0372] (II-2) forming a silicon-containing resist interlayer film on the protective film using a silicon-containing resist interlayer film material,
[0373] (II-3) forming an organic antireflection film on the aforementioned silicon-containing resist intermediate film,
[0374] (II-4) forming a resist upper layer film on the organic antireflection film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film,
[0375] (II-5) using the patterned resist upper layer film as a mask, transferring the pattern to the organic anti-reflective film and the silicon-containing resist intermediate film by etching,
[0376] (II-6) using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask, transferring the pattern to the protective film by etching, and
[0377] (II-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0378] This method can be performed in the same manner as the above-mentioned three-layer resist method using a silicon-containing resist interlayer film, except that an organic antireflection film (BARC) is formed between the silicon-containing resist interlayer film and the resist upper layer film.
[0379] The organic anti-reflection film can be formed by spin coating using a known organic anti-reflection film material.
[0380] [Three-layer resist method using an inorganic hard mask]
[0381] Furthermore, the present invention provides a pattern forming method, which is a method for forming a pattern on a processed substrate, comprising the following steps:
[0382] (III-1) forming a protective film on a substrate to be processed using the protective film forming composition,
[0383] (III-2) forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the protective film,
[0384] (III-3) forming a resist upper layer film on the inorganic hard mask using a photoresist composition,
[0385] (III-4) forming a circuit pattern on the resist upper layer film,
[0386] (III-5) using the patterned resist upper layer film as a mask, transferring the pattern to the inorganic hard mask film by etching,
[0387] (III-6) using the inorganic hard mask film to which the pattern has been transferred as a mask, and transferring the pattern to the protective film by etching, and
[0388] (III-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0389] This method can be performed in the same manner as the above-mentioned three-layer resist method using a silicon-containing resist interlayer film, except that an inorganic hard mask is formed on the protective film instead of forming a silicon-containing resist interlayer film.
[0390] The inorganic hard mask selected from silicon oxide film, silicon nitride film, and silicon oxide nitride film (SiON film) can be formed by CVD method, ALD method, etc. The method of forming silicon nitride film is described in, for example, Japanese Patent Publication No. 2002-334869 and International Publication No. 2004 / 066377. The film thickness of the inorganic hard mask is preferably 5 to 200 nm, more preferably 10 to 100 nm. It is most desirable to use SiON film with high effect as an anti-reflective film as the inorganic hard mask. The substrate temperature when forming the SiON film will become 300 to 500°C, so the lower film needs to withstand a temperature of 300 to 500°C. The protective film formed using the protective film forming composition of the present invention has high heat resistance and can withstand high temperatures of 300 to 500°C, so it can be a combination of an inorganic hard mask formed by CVD method or ALD method and a protective film formed by spin coating method.
[0391] [Four-layer resist method using inorganic hard mask and organic anti-reflective film]
[0392] Furthermore, the present invention provides a pattern forming method, which is a method for forming a pattern on a processed substrate, comprising the following steps:
[0393] (IV-1) forming a protective film on a substrate to be processed using the protective film forming composition,
[0394] (IV-2) forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the protective film,
[0395] (IV-3) forming an organic antireflection film on the inorganic hard mask film,
[0396] (IV-4) forming a resist upper layer film on the organic antireflection film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film,
[0397] (IV-5) using the patterned resist upper layer film as a mask, transferring the pattern to the organic antireflective film and the inorganic hard mask by etching,
[0398] (IV-6) using the inorganic hard mask film to which the pattern has been transferred as a mask, and transferring the pattern to the protective film by etching, and
[0399] (IV-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0400] This method can be performed in the same manner as the above-mentioned three-layer resist process using an inorganic hard mask, except that an organic antireflection film (BARC) is formed between the inorganic hard mask and the resist upper layer film.
[0401] In particular, when a SiON film is used as an inorganic hard mask, the two-layer antireflection film of the SiON film and the BARC can suppress reflection even in high NA immersion exposure exceeding 1.0. Another benefit of forming a BARC is that it has the effect of reducing the tailing of the resist upper film pattern directly on the SiON film.
[0402] Here, an example of a pattern forming method using a three-layer resist process of the present invention is shown. Figure 2 (A)~(F). When the 3-layer resist is processed, Figure 2 As shown in (A), a protective film 3 is formed on a workpiece layer 2 formed on a substrate 1 using the protective film forming composition of the present invention, and then a silicon-containing resist intermediate film 4 is formed, and a resist upper film 5 is formed thereon. Figure 2 As shown in (B), the exposed portion 6 of the resist upper film 5 is exposed and PEB (post-exposure baking) is performed. Figure 2 As shown in (C), development is performed to form a resist upper film pattern 5a. Figure 2 As shown in (D), the resist upper film pattern 5a is used as a mask, and the silicon-containing resist intermediate film 4 is dry-etched using a fluorine-based gas to form a silicon-containing resist intermediate film pattern 4a. Then, as shown in FIG. Figure 2 As shown in (E), after removing the resist upper film pattern 5a, the protective film 3 is subjected to oxygen plasma etching using the silicon-containing resist intermediate film pattern 4a as a mask to form a protective film pattern 3a. Figure 2 As shown in (F), after the silicon-containing resist intermediate film pattern 4a is removed, the processing layer 2 is etched using the protection film pattern 3a as a mask to form a pattern 2a.
[0403] When forming an inorganic hard mask, the silicon-containing resist intermediate film 4 may be replaced with an inorganic hard mask, and when forming a BARC, the BARC may be formed between the silicon-containing resist intermediate film 4 and the resist upper film 5. The etching of the BARC may be performed continuously before the etching of the silicon-containing resist intermediate film 4, or the etching of the silicon-containing resist intermediate film 4 may be performed after only the etching of the BARC and then the etching device may be changed.
[0404] (Special processing)
[0405] Furthermore, if the pattern forming method of the present invention is adopted, in addition to the general processing mentioned above, various special processing can be constructed, and the industrial value is high.
[0406] (First form)
[0407] First, as for the stripping of the silicon-containing resist intermediate film, generally, dry etching stripping is required as described above, but in the pattern forming method of the present invention, the protective film has alkaline hydrogen peroxide water resistance, so it is also an option to wet-strip only the silicon-containing resist intermediate film using alkaline hydrogen peroxide water. That is, in the pattern forming method using the three-layer resist treatment of the present invention, after the above-mentioned step (I-6) or step (II-6), a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water can be added.
[0408] (Second aspect)
[0409] Furthermore, when the substrate to be processed is W, TiN, etc., if the pattern forming method of the present invention is adopted, wet etching of the substrate using alkaline hydrogen peroxide water is also an option. That is, in the pattern forming method of the present invention using a three-layer or four-layer resist process, the etching method of the above-mentioned step (I-7), step (II-7), step (III-7), or step (IV-7) can also be a step of transferring the pattern to the substrate to be processed by wet etching using alkaline hydrogen peroxide water using the protective film to which the pattern has been transferred as a mask.
[0410] In one example of the process at this time, a protective film is first formed on the substrate to be processed, and a silicon-containing resist intermediate film is formed thereon as needed, and then a resist upper film is formed. Then, the resist upper film is patterned according to the usual method, and then the pattern is transferred to the protective film by etching. Finally, the protective film is used as a mask to pattern the substrate to be processed by wet etching.
[0411] (Third Pattern)
[0412] Furthermore, in the pattern forming method using three-layer or four-layer resist processing of the present invention, the above-mentioned step (I-7), step (II-7), step (III-7), or step (IV-7) may be a step of patterning the substrate to be processed by ion implantation using the protective film to which the pattern has been transferred as a mask. In this case, after the step of patterning the substrate to be processed by ion implantation, a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water may be added.
[0413] Furthermore, the pattern forming method of the present invention is also suitable for processing a structure having a height of 30 nm or more or a step-difference substrate. An example of such a process is described below.
[0414] First, a protective film is formed on the high-low substrate, and buried and flattened. After forming a silicon-containing resist intermediate film as needed, a resist upper film is formed. Then, the resist upper film is patterned according to the usual method, and then the pattern is transferred to the protective film by etching. Then, the protective film is used as a mask, and the substrate can be patterned by ion implantation. The remaining silicon-containing resist intermediate film can be stripped off by dry etching or wet etching as needed. Finally, the protective film can be removed by dry etching.
[0415] As described above, according to the pattern forming method of the present invention, a fine pattern can be formed on a substrate to be processed with high precision using a multilayer resist method.
[0416] [Example]
[0417] The present invention is described in more detail below with reference to Synthesis Examples, Comparative Synthesis Examples, Examples, and Comparative Examples, but the present invention is not limited thereto. The molecular weight and dispersity are obtained by determining the weight average molecular weight (Mw) and number average molecular weight (Mn) in terms of polystyrene obtained by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent, and determining the dispersity (Mw / Mn).
[0418] [Synthesis Example: Synthesis of a polymer for protective film forming composition and a polymer having a hydroxyl group at the terminal group]
[0419] The synthesis of polymers (or polymer mixtures) (A1) to (A9) for forming a protective film composition and polymers (A10) to (A12) having a hydroxyl group at the terminal group uses the following tetracarboxylic anhydrides (B1) to (B5), diamine compounds (C1) to (C8), and aniline derivatives and phthalic anhydride derivatives (D1) to (D10) as end-capping agents.
[0420] Tetracarboxylic anhydride:
[0421] [Chemistry 49]
[0422]
[0423] Diamine compounds:
[0424] [Chemistry 50]
[0425]
[0426] Capping agent:
[0427] [Chemistry 51]
[0428]
[0429] [Synthesis Example 1] Synthesis of polymer (A1)
[0430] 120 g of NMP (N-methyl-2-pyrrolidone) was added to 17.77 g of tetracarboxylic anhydride (B1) and 10.65 g of diamine compound (C1), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 3.15 g of end-capping agent (D1) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 150 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 400 g of methyl isobutyl ketone was added, the organic layer was washed twice with 100 g of 3% nitric acid aqueous solution, and then washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 400 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 300 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (A1). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0431] [Chemistry 52]
[0432]
[0433] (A1): Mw=3750, Mw / Mn=1.66
[0434] [Synthesis Example 2] Synthesis of polymer (A2)
[0435] 90 g of NMP (N-methyl-2-pyrrolidone) was added to 15.61 g of tetracarboxylic anhydride (B2), 2.51 g of diamine compound (C2) and 1.94 g of diamine compound (C3), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 5.80 g of end-capping agent (D2) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 120 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 300 g of methyl isobutyl ketone was added, the organic layer was washed twice with 75 g of 3% nitric acid aqueous solution, and then washed 6 times with 75 g of pure water, and the organic layer was dried under reduced pressure. 75 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 300 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 200 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain polymer (A2). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.
[0436] [Chemistry 53]
[0437]
[0438] (A2): Mw=2480, Mw / Mn=1.42
[0439] [Synthesis Example 3] Synthesis of polymer (A3)
[0440] 90 g of NMP (N-methyl-2-pyrrolidone) was added to 19.28 g of tetracarboxylic anhydride (B3), 1.92 g of diamine compound (C4) and 1.30 g of diamine compound (C5), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 4.22 g of end-capping agent (D3) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 120 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 300 g of methyl isobutyl ketone was added, the organic layer was washed twice with 75 g of 3% nitric acid aqueous solution, and then washed 6 times with 75 g of pure water, and the organic layer was dried under reduced pressure. 75 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 300 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 200 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain polymer (A3). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.
[0441] [Chemistry 54]
[0442]
[0443] (A3): Mw=2180, Mw / Mn=1.28
[0444] [Synthesis Example 4] Synthesis of polymer mixture (A4)
[0445] The polymer (A4-1) and the polymer (A4-2) used in the polymer mixture (A4) were synthesized as follows.
[0446] [Synthesis Example 4-1] Synthesis of polymer (A4-1)
[0447] 60 g of NMP (N-methyl-2-pyrrolidone) was added to 6.36 g of tetracarboxylic anhydride (B4) and 3.84 g of diamine compound (C6), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 2.34 g of end-capping agent (D4) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 80 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 200 g of methyl isobutyl ketone was added, the organic layer was washed twice with 50 g of 3% nitric acid aqueous solution, and then washed 6 times with 50 g of pure water, and the organic layer was dried under reduced pressure. 50 g of THF (tetrahydrofuran) was added to the residue, and after a uniform solution was prepared, 200 g of diisopropyl ether was used for crystallization. The precipitated crystals were separated by filtration, washed twice with 150 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (A4-1). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0448] [Chemistry 55]
[0449]
[0450] (A4-1): Mw=2310, Mw / Mn=1.45
[0451] [Synthesis Example 4-2] Synthesis of polymer (A4-2)
[0452] 60 g of NMP (N-methyl-2-pyrrolidone) was added to 6.36 g of tetracarboxylic anhydride (B4) and 2.58 g of diamine compound (C3), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 2.34 g of end-capping agent (D4) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 80 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 200 g of methyl isobutyl ketone was added, the organic layer was washed twice with 50 g of 3% nitric acid aqueous solution, and then washed 6 times with 50 g of pure water, and the organic layer was dried under reduced pressure. 50 g of THF (tetrahydrofuran) was added to the residue, and after a uniform solution was prepared, 200 g of diisopropyl ether was used for crystallization. The precipitated crystals were separated by filtration, washed twice with 150 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (A4-2). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0453] [Chemistry 56]
[0454]
[0455] (A4-2): Mw=2190, Mw / Mn=1.43
[0456] [Synthesis Example 5] Synthesis of polymer (A5)
[0457] 45 g of NMP (N-methyl-2-pyrrolidone) was added to 9.64 g of tetracarboxylic anhydride (B3) and 2.20 g of diamine compound (C7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 3.48 g of end-capping agent (D2) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 60 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 150 g of methyl isobutyl ketone was added, the organic layer was washed twice with 40 g of 3% nitric acid aqueous solution, and then washed 6 times with 40 g of pure water, and the organic layer was dried under reduced pressure. 40 g of THF (tetrahydrofuran) was added to the residue, and after a uniform solution was prepared, 150 g of diisopropyl ether was used for crystallization. The precipitated crystals were separated by filtration, washed twice with 120 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (A5). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0458] [Chemistry 57]
[0459]
[0460] (A5): Mw=2230, Mw / Mn=1.22
[0461] [Synthesis Example 6] Synthesis of polymer (A6)
[0462] 100 g of NMP (N-methyl-2-pyrrolidone) was added to 10.88 g of tetracarboxylic anhydride (B1) and 12.82 g of diamine compound (C7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 1.95 g of end-capping agent (D5) and 2.61 g of end-capping agent (D6) were added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 130 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 350 g of methyl isobutyl ketone was added, and the organic layer was washed twice with 90 g of 3% nitric acid aqueous solution, and then washed 6 times with 90 g of pure water, and the organic layer was dried under reduced pressure. 90 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 350 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 250 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain polymer (A6). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.
[0463] [Chemistry 58]
[0464]
[0465] (A6): Mw=3950, Mw / Mn=1.70
[0466] [Synthesis Example 7] Synthesis of polymer (A7)
[0467] 75 g of NMP (N-methyl-2-pyrrolidone) was added to 15.71 g of tetracarboxylic anhydride (B5) and 3.66 g of diamine compound (C7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 3.51 g of end-capping agent (D3) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 90 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 250 g of methyl isobutyl ketone was added, the organic layer was washed twice with 60 g of 3% nitric acid aqueous solution, and then washed 6 times with 60 g of pure water, and the organic layer was dried under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue, and after a uniform solution was prepared, 250 g of diisopropyl ether was used for crystallization. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (A7). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0468] [Chemistry 59]
[0469]
[0470] (A7): Mw=1950, Mw / Mn=1.21
[0471] [Synthesis Example 8] Synthesis of polymer (A8)
[0472] 75 g of NMP (N-methyl-2-pyrrolidone) was added to 7.86 g of tetracarboxylic anhydride (B5), 9.07 g of diamine compound (C8) and 2.75 g of diamine compound (C7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 4.30 g of end-capping agent (D7) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 90 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 250 g of methyl isobutyl ketone was added, and the organic layer was washed twice with 60 g of 3% nitric acid aqueous solution, and then washed 6 times with 60 g of pure water, and the organic layer was dried under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 250 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain polymer (A8). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.
[0473] [Chemistry 60]
[0474]
[0475] (A8): Mw=2560, Mw / Mn=1.41
[0476] [Synthesis Example 9] Synthesis of polymer (A9)
[0477] 40 g of NMP (N-methyl-2-pyrrolidone) was added to 7.54 g of tetracarboxylic anhydride (B5), 0.80 g of diamine compound (C2) and 0.88 g of diamine compound (C7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 1.69 g of end-capping agent (D4) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 45 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 120 g of methyl isobutyl ketone was added, and the organic layer was washed twice with 30 g of 3% nitric acid aqueous solution, and then washed 6 times with 30 g of pure water, and the organic layer was dried under reduced pressure. 30 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 120 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 90 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain polymer (A9). The weight average molecular weight (Mw) and dispersity (Mw / Mn) were determined by GPC, and the following results were obtained.
[0478] [Chemistry 61]
[0479]
[0480] (A9): Mw=2010, Mw / Mn=1.29
[0481] [Synthesis Example 10] Synthesis of polymer (A10)
[0482] 75 g of NMP (N-methyl-2-pyrrolidone) was added to 16.07 g of tetracarboxylic anhydride (B3) and 3.34 g of diamine compound (C2), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 3.27 g of end-capping agent (D8) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 90 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 250 g of methyl isobutyl ketone was added, the organic layer was washed twice with 60 g of 3% nitric acid aqueous solution, and then washed 6 times with 60 g of pure water, and the organic layer was dried under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue, and after a uniform solution was prepared, 250 g of diisopropyl ether was used for crystallization. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (A10). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0483] [Chemistry 62]
[0484]
[0485] (A10): Mw=1970, Mw / Mn=1.24
[0486] [Synthesis Example 11] Synthesis of polymer (A11)
[0487] 75 g of NMP (N-methyl-2-pyrrolidone) was added to 16.07 g of tetracarboxylic anhydride (B3) and 3.66 g of diamine compound (C7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 4.17 g of end-capping agent (D9) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 90 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 250 g of methyl isobutyl ketone was added, the organic layer was washed twice with 60 g of 3% nitric acid aqueous solution, and then washed 6 times with 60 g of pure water, and the organic layer was dried under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue, and after a uniform solution was prepared, 250 g of diisopropyl ether was used for crystallization. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (A11). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0488] [Chemistry 63]
[0489]
[0490] (A11): Mw=2010, Mw / Mn=1.23
[0491] [Synthesis Example 12] Synthesis of polymer (A12)
[0492] 75 g of NMP (N-methyl-2-pyrrolidone) was added to 15.71 g of tetracarboxylic anhydride (B5) and 5.18 g of diamine compound (C8), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 4.78 g of end-capping agent (D10) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 90 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 250 g of methyl isobutyl ketone was added, the organic layer was washed twice with 60 g of 3% nitric acid aqueous solution, and then washed 6 times with 60 g of pure water, and the organic layer was dried under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue, and after a uniform solution was prepared, 250 g of diisopropyl ether was used for crystallization. The precipitated crystals were separated by filtration, washed twice with 180 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (A12). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0493] [Chemistry 64]
[0494]
[0495] (A12): Mw=2100, Mw / Mn=1.25
[0496] The polymers (R1) to (R9) used in the comparative examples were synthesized using the following compounds (E1) to (E10), the aforementioned tetracarboxylic anhydrides (B1), (B3), (B5), the diamine compounds (C1), (C7), (C8), and the end-capping agents (D3), (D6), and (D7). (E10) was a 60:40 isomer mixture.
[0497] [Chemistry 65]
[0498]
[0499] [Synthesis Example 13] Synthesis of polymer (R1)
[0500] 120 g of NMP (N-methyl-2-pyrrolidone) was added to 7.11 g of tetracarboxylic anhydride (B1) and 14.65 g of diamine compound (C7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 7.11 g of (E1) as a capping agent was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 150 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 400 g of methyl isobutyl ketone was added, the organic layer was washed twice with 100 g of 3% nitric acid aqueous solution, and then washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 400 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 300 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (R1). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0501] [Chemistry 66]
[0502]
[0503] (R1): Mw=2250, Mw / Mn=1.32
[0504] [Synthesis Example 14] Synthesis of polymer (R2)
[0505] 90 g of NMP (N-methyl-2-pyrrolidone) was added to 13.33 g of tetracarboxylic anhydride (B1) and 4.40 g of diamine compound (C7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 3.35 g of (E2) as a capping agent was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 120 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 300 g of methyl isobutyl ketone was added, the organic layer was washed twice with 75 g of 3% nitric acid aqueous solution, and then washed 6 times with 75 g of pure water, and the organic layer was dried under reduced pressure. 75 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 300 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 200 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (R2). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0506] [Chemistry 67]
[0507]
[0508] (R2): Mw=2140, Mw / Mn=1.29
[0509] [Synthesis Example 15] Synthesis of polymer (R3)
[0510] 120 g of NMP (N-methyl-2-pyrrolidone) was added to 12.57 g of tetracarboxylic anhydride (B5) and 14.65 g of diamine compound (C7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 3.92 g of (E3) as a capping agent was added to the obtained polyamic acid intermediate solution, and the mixture was reacted for another 3 hours at an internal temperature of 40°C to obtain a polyimide precursor solution. 150 g of o-xylene was added to the obtained reaction solution, and the mixture was reacted for 9 hours at an internal temperature of 180°C while removing the generated water from the system to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 400 g of methyl isobutyl ketone was added, and the organic layer was washed twice with 100 g of 3% nitric acid aqueous solution, and then washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 400 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 300 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (R3). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0511] [Chemistry 68]
[0512]
[0513] (R3): Mw=2360, Mw / Mn=1.36
[0514] [Synthesis Example 16] Synthesis of polymer (R4)
[0515] To 30.00 g of tetracarboxylic anhydride (B1) was added 150 g of N-methylpyrrolidone, and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen environment. Then, 14.74 g of an amine compound (E4) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system to carry out dehydration imidization. After the reaction was completed, the mixture was cooled to room temperature and crystallized with 1000 g of diisopropyl ether. The precipitated crystals were separated by filtration, washed twice with 500 g of diisopropyl ether, and recovered. The recovered crystals were vacuum dried at 70°C to obtain the amide compound (R4').
[0516] [Chemistry 69]
[0517]
[0518] Then, 15.00 g of the obtained imide compound (R4'), 1.36 g of the aldehyde compound (E5), and 60 g of 2-methoxy-1-propanol were prepared into a uniform solution at an internal temperature of 80°C under a nitrogen environment, and 1.5 g of a 20% p-toluenesulfonic acid 2-methoxy-1-propanol solution was slowly added, and stirred at an internal temperature of 110°C for 8 hours. After cooling to room temperature, 200 g of methyl isobutyl ketone was added, and the organic layer was washed 5 times with 50 g of pure water, and then the organic layer was dried under reduced pressure. 50 g of THF was added to the residue, and the polymer was reprecipitated with 200 g of hexane. The precipitated polymer was separated by filtration and dried under reduced pressure to obtain a polymer (R4). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0519] [Chemistry 70]
[0520]
[0521] (R4): Mw=2820, Mw / Mn=1.72
[0522] [Synthesis Example 17] Synthesis of polymer (R5)
[0523] 120 g of NMP (N-methyl-2-pyrrolidone) was added to 15.55 g of tetracarboxylic anhydride (B1) and 14.62 g of diamine compound (E6), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 5.16 g of end-capping agent (D7) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 4.00 g of pyridine was added to the obtained reaction solution, and 12.25 g of acetic anhydride was slowly added dropwise, and the mixture was reacted at an internal temperature of 60°C for 4 hours to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 400 g of methyl isobutyl ketone was added, the organic layer was washed twice with 100 g of 3% nitric acid aqueous solution, and then washed 6 times with 100 g of pure water, and the organic layer was dried under reduced pressure. 100 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 400 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (R5). The weight average molecular weight (Mw) and the dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0524] [Chemistry 71]
[0525]
[0526] (R5): Mw=4320, Mw / Mn=1.72
[0527] [Synthesis Example 18] Synthesis of polymer (R6)
[0528] 70 g of NMP (N-methyl-2-pyrrolidone) was added to 13.33 g of tetracarboxylic anhydride (B1) and 7.32 g of diamine compound (E7), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 2.11 g of end-capping agent (D3) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 2.37 g of pyridine was added to the obtained reaction solution, and 7.35 g of acetic anhydride was slowly added dropwise, and the mixture was reacted at an internal temperature of 60°C for 4 hours to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 240 g of methyl isobutyl ketone was added, the organic layer was washed twice with 60 g of 3% nitric acid aqueous solution, and then washed 6 times with 60 g of pure water, and the organic layer was dried under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 240 g of methanol. The precipitated crystals were separated by filtration, washed twice with 240 g of methanol, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (R6). The weight average molecular weight (Mw) and the dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0529] [Chemistry 72]
[0530]
[0531] (R6): Mw=3780, Mw / Mn=1.67
[0532] [Synthesis Example 19] Synthesis of polymer (R7)
[0533] 70 g of NMP (N-methyl-2-pyrrolidone) was added to 7.71 g of tetracarboxylic anhydride (B3) and 15.55 g of diamine compound (C8), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 6.20 g of end-capping agent (D7) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 2.37 g of pyridine was added to the obtained reaction solution, and 7.35 g of acetic anhydride was slowly added dropwise, and the mixture was reacted at an internal temperature of 60°C for 4 hours to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 240 g of methyl isobutyl ketone was added, the organic layer was washed twice with 60 g of 3% nitric acid aqueous solution, and then washed 6 times with 60 g of pure water, and the organic layer was dried under reduced pressure. 60 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 240 g of methanol. The precipitated crystals were separated by filtration, washed twice with 240 g of methanol, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (R7). The weight average molecular weight (Mw) and the dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0534] [Chemistry 73]
[0535]
[0536] (R7): Mw=2420, Mw / Mn=1.26
[0537] [Synthesis Example 20] Synthesis of polymer (R8)
[0538] 100 g of NMP (N-methyl-2-pyrrolidone) was added to 18.34 g of tetracarboxylic anhydride (E8) and 8.30 g of diamine compound (C8), and the mixture was reacted at an internal temperature of 40°C for 3 hours under a nitrogen environment. 5.62 g of end-capping agent (D3) was added to the obtained polyamic acid intermediate solution, and the mixture was reacted at an internal temperature of 40°C for another 3 hours to obtain a polyimide precursor solution. 3.16 g of pyridine was added to the obtained reaction solution, and 9.80 g of acetic anhydride was slowly added dropwise, and the mixture was reacted at an internal temperature of 60°C for 4 hours to perform imidization. After the reaction was completed, the mixture was cooled to room temperature, 320 g of methyl isobutyl ketone was added, the organic layer was washed twice with 80 g of 3% nitric acid aqueous solution, and then washed 6 times with 80 g of pure water, and the organic layer was dried under reduced pressure. 80 g of THF (tetrahydrofuran) was added to the residue to make a uniform solution, and then crystallized with 320 g of methanol. The precipitated crystals were separated by filtration, washed twice with 240 g of methanol, and recovered. The recovered crystals were vacuum dried at 70°C to obtain a polymer (R8). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0539] [Chemistry 74]
[0540]
[0541] (R8): Mw=2240, Mw / Mn=1.27
[0542] [Synthesis Example 21] Synthesis of polymer (R9)
[0543] Add 50 g of THF to 6.32 g of compound (E9) to make a uniform solution in an ice bath under a nitrogen atmosphere. Slowly drop 4.00 g of diamine compound (E10) and 3.34 g of triethylamine dissolved in 20 g of NMP in advance, and react at room temperature for 1 hour. Then, add 14.28 g of compound (C1) and 100 g of NMP to the reaction solution, react at an internal temperature of 40°C for 3 hours, and then add 11.18 g of end-capping agent (D6) to obtain a polyimide precursor. Add 150 g of o-xylene to the obtained reaction solution, and react for 9 hours at an internal temperature of 180°C while removing the generated low-boiling substances and generated water from the system to perform imidization. After the reaction is completed, cool to room temperature and crystallize with 600 g of diisopropyl ether. Separate the precipitated crystals by filtration, wash twice with 200 g of diisopropyl ether, and recover them. Dry the recovered crystals in a vacuum at 70°C to obtain (R9). The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the following results were obtained.
[0544] [Chemistry 75]
[0545]
[0546] (R9): Mw=2930, Mw / Mn=1.42
[0547] [Preparation of protective film forming compositions (UDL-1 to 22, comparative UDL-1 to 9)]
[0548] The above polymers (A1) to (A12) and (R1) to (R9) and high boiling point solvents (S1) 1,6-diacetoxyhexane: boiling point 260° C., (S2) γ-butyrolactone: boiling point 204° C., and (S3) tripropylene glycol monomethyl ether: boiling point 242° C. were used. Propylene glycol monomethyl ether acetate (PGMEA) and cyclohexanone (CyHO) containing 0.1% by mass of FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) were dissolved in the ratios shown in Table 1, and filtered with a 0.1 μm fluororesin filter to prepare protective film-forming compositions (UDL-1 to 22, comparative UDL-1 to 9).
[0549] [Table 1]
[0550]
[0551]
[0552] [Example 1 Solvent Resistance Measurement (Examples 1-1 to 1-22, Comparative Examples 1-1 to 1-9)]
[0553] The protective film forming composition (UDL-1 to 22, comparative UDL-1 to 9) prepared above was coated on a silicon substrate, and calcined at 450°C for 60 seconds under a nitrogen flow with an oxygen concentration of less than 0.2%, and the film thickness was measured. PGMEA solvent was dispensed thereon, left for 30 seconds and spin-dried, and baked at 100°C for 60 seconds to evaporate PGMEA, and the film thickness was measured, and the difference in film thickness before and after PGMEA treatment was calculated. The results are shown in Table 2.
[0554] [Table 2]
[0555]
[0556]
[0557] As shown in Table 2, the residual film rate of the protective film forming composition of the present invention (Examples 1-1 to 1-22) after PGMEA treatment is more than 99%, and even in a nitrogen environment, a cross-linking reaction will still occur, showing sufficient solvent resistance. In contrast, the comparative examples 1-1, 1-2, and 1-4 using polyimide without cross-linking groups have a residual film rate of about 70% after PGMEA treatment, which does not show sufficient solvent resistance. From these results, it can be seen that R1 introduced as a substituent effectively functions as a thermal cross-linking group.
[0558] [Example 2 Evaluation of heat resistance characteristics (Examples 2-1 to 2-22, Comparative Examples 2-1 to 2-9)]
[0559] The protective film forming compositions (UDL-1 to 22, comparative UDL-1 to 9) were coated on silicon substrates, respectively, and fired at 180°C for 60 seconds in air to form a 200 nm coating film, and the film thickness A was measured. The substrate was further fired at 450°C for 10 minutes under a nitrogen flow controlled to an oxygen concentration of 0.2% or less, and the film thickness B was measured. These results are shown in Table 3.
[0560] [Table 3]
[0561]
[0562] As shown in Table 3, it can be seen that the protective film forming composition of the present invention (Examples 2-1 to 2-22) has a film thickness reduction of less than 1% even after calcination at 450°C. The protective film forming composition of the present invention still maintains the film thickness before high-temperature baking after calcination at 450°C, and has high heat resistance. On the other hand, compared with Comparative Examples 2-1, 2-2, and 2-4 using polyimide without cross-linking groups, the protective film forming composition of the present invention forms a dense film by thermal crosslinking using the terminal crosslinking group R1, and will form a film with excellent heat resistance. In addition, it can be seen that Comparative Example 2-3 having a bismaleimide structure as a crosslinking group will exhibit solvent resistance due to thermal crosslinking under the conditions of Example 1, but under the conditions of long-term high-temperature treatment as in Example 2, it does not exhibit sufficient heat resistance due to thermal crosslinking using the bismaleimide structure.
[0563] [Evaluation of landfill characteristics in Example 3 (Examples 3-1 to 3-22, Comparative Examples 3-1 to 3-9)]
[0564] like Figure 3 The protective film forming compositions (UDL-1 to 22, comparative UDL-1 to 9) were coated on SiO2 wafer substrates with dense hole patterns (hole diameter 0.16 μm, hole depth 0.50 μm, distance between the centers of two adjacent holes 0.32 μm), and calcined at 450°C for 60 seconds using a hot plate under a nitrogen flow with an oxygen concentration of less than 0.2%, to form protective film 8. The substrate used was Figure 3 The base substrate 7 (SiO2 wafer substrate) with a dense hole pattern shown in (G) (bird's-eye view) and (H) (cross-sectional view). The cross-sectional shape of each wafer substrate obtained was observed using a scanning electron microscope (SEM) to confirm whether there were no pores (voids) inside the holes and they were filled with a protective film. The results are shown in Table 4. When a protective film-forming composition with poor filling characteristics was used, pores appeared inside the holes in this evaluation. When a protective film-forming composition with good filling characteristics was used, in this evaluation, Figure 3 As shown in (I), the inside of the pores is filled with the protective film without any voids.
[0565] [Table 4]
[0566]
[0567]
[0568] As shown in Table 4, the protective film forming composition of the present invention (Examples 3-1 to 3-22) can fill the hole pattern without voids, and it is confirmed that they have good filling characteristics. On the other hand, it is confirmed that the Comparative Examples 3-1 to 3-4 have voids and poor filling characteristics. From this result, it can be seen that the protective film forming composition of the present invention has improved filling characteristics due to the heat hardening reaction to ensure heat resistance. On the other hand, even in Comparative Examples 3-1 to 3-4, UDL-3, which shows solvent resistance, still has voids due to insufficient heat resistance, and good filling characteristics are not obtained.
[0569] [Example 4 Evaluation of Flattening Characteristics (Examples 4-1 to 4-22, Comparative Examples 4-1 to 4-9)]
[0570] The protective film forming compositions (UDL-1 to 22, comparative UDL-1 to 9) were coated on the surfaces having a giant isolated trench pattern ( Figure 4 On a base substrate 9 (SiO2 wafer substrate) with a groove width of 10 μm and a groove depth of 0.10 μm, after calcination at 450°C for 60 seconds under a nitrogen flow with an oxygen concentration of less than 0.2%, the height difference of the protective film 10 between the groove part and the non-groove part was observed using an NX10 atomic force microscope (AFM) manufactured by PARK SYSTEMS Co., Ltd. Figure 4 The results are shown in Table 5. In this evaluation, the smaller the height difference, the better the planarization characteristics. In this evaluation, the trench pattern with a depth of 0.10 μm is planarized using a protective film forming composition with a film thickness of about 0.2 μm, which becomes a strict evaluation condition for evaluating the quality of the planarization characteristics.
[0571] [Table 5]
[0572]
[0573] As shown in Table 5, it is confirmed that the protective film forming composition of the present invention (Examples 4-1 to 4-22) has a smaller height difference between the trench part and the non-ditch part of the protective film than Comparative Examples 4-1 to 4-4, and has excellent flattening characteristics. In Comparative Example 4-3, as the result of the heat resistance evaluation of Example 2, the heat resistance is poor, so the film loss caused by high-temperature baking is large, so the film thickness difference between the upper and lower parts of the height difference is emphasized, and the flatness is deteriorated, resulting in the above result. Comparative Examples 4-1, 4-2, and 4-4 also use non-crosslinked polyimide, so the film loss caused by high-temperature treatment has a great impact, resulting in poor flatness. In addition, it can be seen that Examples 4-11 to 4-13, 4-20 to 4-22 to which a high boiling point solvent is added have improved flatness due to the addition of a high boiling point solvent compared with Examples 4-3, 4-5, 4-7, and 4-17 to 4-19 to which no high boiling point solvent is added.
[0574] [Example 5 Evaluation of resistance to alkaline hydrogen peroxide water (Examples 5-1 to 5-22, Comparative Examples 5-1 to 5-9)]
[0575] The above protective film forming compositions (UDL-1 to 22, comparative UDL-1 to 9) were coated on silicon wafer substrates with a 300nm SiO2 film formed thereon, and calcined at 450°C for 60 seconds under a nitrogen flow with an oxygen concentration of less than 0.2% to form a protective film (resist lower layer film) with a film thickness of 200nm. Then, the wafer was cut into pieces with a width of 2cm, and the wafer was immersed in a 1.0% by mass hydrogen peroxide solution containing 0.5% by mass of ammonia at 70°C for 5 minutes. After rinsing with deionized water and drying, it was visually inspected whether the protective film was peeled off from the wafer. When part or all of the protective film peeled off and the surface of the silicon wafer was exposed, it was judged that the alkaline hydrogen peroxide water resistance of the protective film to be tested was insufficient. These evaluation results are shown in Table 6.
[0576] [Table 6]
[0577]
[0578]
[0579] As shown in Table 6, the protective film forming composition of the present invention (Examples 5-1 to 5-22) did not show peeling of the protective film. On the other hand, although Comparative Examples 5-1 to 5-9 ensured heat resistance and solvent resistance, peeling of the protective film was observed. It can be seen from this that the polyimide compound in which fluorine atoms and hydroxyl groups coexist as in the present invention has excellent alkaline hydrogen peroxide resistance. It can also be seen that even if a polyimide having a hydroxyl group at the terminal group is added, the alkaline hydrogen peroxide resistance is still excellent.
[0580] [Example 6 Pattern Formation Test (Examples 6-1 to 6-22, Comparative Examples 6-1 to 6-9)]
[0581] The protective film forming compositions (UDL-1 to 22, comparative UDL-1 to 9) were coated on a silicon wafer substrate with a 300 nm SiO2 film formed thereon, and calcined at 450°C for 60 seconds in a nitrogen flow controlled to an oxygen concentration of 0.2% or less to form a protective film (resist lower layer film) with a film thickness of 200 nm. A CVD-SiON hard mask was formed thereon, and an organic anti-reflection film material (ARC-29A: manufactured by Nissan Chemical Co., Ltd.) was coated thereon, and baked at 210°C for 60 seconds to form an organic anti-reflection film with a film thickness of 80 nm. A single-layer resist for ArF, which was a resist upper layer film material, was coated thereon, and baked at 105°C for 60 seconds to form a photoresist film with a film thickness of 100 nm. A wet protective film material (TC-1) was coated on the photoresist film, and baked at 90°C for 60 seconds to form a protective film with a film thickness of 50 nm.
[0582] The resist upper film material (single-layer resist for ArF) is prepared by dissolving a polymer (RP1), an acid generator (PAG1), and a basic compound (Amine1) according to the proportions shown in Table 7 in a solvent containing 0.1% by mass of FC-430 (manufactured by Sumitomo 3M Co., Ltd.), and filtering with a 0.1 μm fluororesin filter.
[0583] [Table 7]
[0584]
[0585] The polymer (RP1), the acid generator (PAG1), and the basic compound (Amine1) used for the resist upper layer film material (single-layer resist for ArF) are shown below.
[0586] [Chemistry 76]
[0587]
[0588] [Chemistry 77]
[0589]
[0590] The wet protective film material (TC-1) was prepared by dissolving the protective film polymer (PP1) in an organic solvent according to the ratio shown in Table 8 and filtering the solution with a 0.1 μm fluororesin filter.
[0591] [Table 8]
[0592]
[0593] The polymer (PP1) used in the wet protection film material (TC-1) is shown below.
[0594] [Chemistry 78]
[0595]
[0596] Next, the film was exposed with an ArF immersion exposure device (manufactured by Nikon Co., Ltd.; NSR-S610C, NA1.30, σ0.98 / 0.65, 35-degree dipole s-polarized illumination, 6% half-step phase shift mask), baked (PEB) at 100°C for 60 seconds, and developed with a 2.38% by mass tetramethylammonium hydroxide (TMAH) aqueous solution for 30 seconds to obtain a 55nm 1:1 positive line and space pattern.
[0597] Next, using a Tokyo Electron etching apparatus Telius, the organic anti-reflective film and the CVD-SiON hard mask were etched by dry etching using the resist pattern as a mask to form a hard mask pattern, and the protective film was etched using the obtained hard mask pattern as a mask to form a protective film pattern. The etching conditions are as follows.
[0598] Transfer conditions of resist pattern to SiON hard mask.
[0599] Chamber pressure 10.0Pa
[0600] RF power 1,500W
[0601] CF4 gas flow rate 75sccm
[0602] O2 gas flow rate 15sccm
[0603] Time 15 sec
[0604] Transfer conditions of the hard mask pattern to the protective film.
[0605] Chamber pressure 2.0Pa
[0606] RF power 500W
[0607] Ar gas flow rate: 75 sccm
[0608] O2 gas flow rate 45sccm
[0609] Time: 120 seconds
[0610] Whether the protective film pattern is formed is confirmed by observing the wafer after the protective film is etched with a top-down SEM view. Then, the wafer is cut into 2 cm wide pieces, and the wafer is immersed in 1.0 mass% hydrogen peroxide water containing 0.5 mass% ammonia at 70°C for 5 minutes, rinsed with deionized water, dried, and then observed using an optical microscope to evaluate whether the protective film pattern is peeled off. These evaluation results are shown in Table 9.
[0611] [Table 9]
[0612]
[0613] As shown in Table 9, the results of the protective film forming composition of the present invention (Examples 6-1 to 6-22) all show that the resist upper film pattern is well transferred to the protective film, confirming that the protective film forming composition of the present invention is suitable for use in micro-processing using a multilayer resist method. Furthermore, it can also be confirmed that the formed protective film pattern has good resistance to alkaline hydrogen peroxide water. Although Comparative Example 6-3 has insufficient heat resistance, it can form a pattern. Furthermore, although Comparative Examples 6-1, 6-2, and 6-4 have insufficient heat resistance and thus solvent resistance, they can form a pattern. On the other hand, even if Comparative Examples 6-1 to 6-9 ensure heat resistance and solvent resistance, it can be seen that the formed protective film pattern is peeled off. Therefore, the protective film forming composition and pattern forming method of the present invention are particularly useful in the manufacture of semiconductor devices that can be processed by a combination of chemical etching using alkaline hydrogen peroxide water and micro-processing using a multilayer resist method.
[0614] [Example 7 Pattern Formation Test (Examples 7-1 to 7-22, Comparative Examples 7-1 to 7-9)]
[0615] The above protective film forming compositions (UDL-1 to 22, comparative UDL-1 to 9) were coated on SiO2 wafer substrates with trench patterns (trench width 10 μm, trench depth 0.10 μm), and calcined at 450°C for 60 seconds under a nitrogen flow with an oxygen concentration of less than 0.2%. The coating film was formed in the same manner as in Example 6, and patterning and dry etching were performed to form a protective film pattern. Furthermore, the obtained protective film pattern was used as a mask to perform etching of the SiO2 film. The etching conditions are as shown below.
[0616] Transfer conditions of protective film pattern to SiO2 film.
[0617] Chamber pressure 2.0Pa
[0618] RF power 2,200W
[0619] C5F 12 Gas flow rate 20sccm
[0620] C2F6 gas flow rate 10sccm
[0621] Ar gas flow rate 300 sccm
[0622] O2 gas flow rate 60sccm
[0623] Time 90 sec
[0624] The results are shown in Table 10 when the pattern cross section was observed using an electron microscope (S-4700) manufactured by Hitachi, Ltd.
[0625] [Table 10]
[0626]
[0627] As shown in Table 10, the results of the protective film forming composition of the present invention (Examples 7-1 to 7-22) all show that the resist upper film pattern is finally well transferred to the substrate, confirming that the protective film forming composition of the present invention can be ideally used in micro-processing using a multilayer resist method. On the other hand, although comparative examples 7-1 to 7-4 can ensure heat resistance and solvent resistance, due to poor pattern filling, pattern collapse occurs during pattern processing, and ultimately a good pattern cannot be obtained.
[0628] From the above, if it is the protective film forming composition of the present invention, it can still take into account the heat resistance above 400°C and the high degree of filling / planarization characteristics even under an oxygen-free inert gas, so it is very useful as a protective film forming composition used in the multilayer resist method, and if it is the pattern forming method of the present invention using this composition, even if the processed body is a substrate with a height difference, it can still form a fine pattern with high precision, so it can be suitable for use in multilayer resist processing for fine patterning in semiconductor device manufacturing, and is particularly suitable for multilayer resist processing including wet etching processing, which is very useful in industry.
[0629] This specification includes the following inventions.
[0630] [1]: A protective film-forming composition for alkaline hydrogen peroxide solution, comprising: (A) a polymer having fluorine atoms and hydroxyl groups represented by any one of the following (I) and (II), or a mixture of a polymer having fluorine atoms and a polymer having hydroxyl groups represented by the following (III), and (B) an organic solvent.
[0631] (I) A polymer having a repeating unit represented by the following general formula (1A) containing at least one fluorine atom and a hydroxyl group and having a terminal group represented by any one of the following general formulas (1B) and (1C),
[0632] (II) a polymer having a repeating unit containing at least one fluorine atom represented by the following general formula (2A) and a repeating unit containing at least one hydroxyl group represented by the following general formula (3A), and the terminal group is a group represented by any one of the following general formulas (1B) and (1C),
[0633] (III) a mixture of a polymer having a repeating unit containing at least one fluorine atom represented by the following general formula (2A) and having a terminal group represented by any one of the following general formulas (1B) and (1C), and a polymer having a repeating unit containing at least one hydroxyl group represented by the following general formula (3A) and having a terminal group represented by any one of the following general formulas (1B) and (1C),
[0634] [Chemistry 79]
[0635]
[0636] In the formula, W1 is one or more tetravalent organic groups which may also contain fluorine atoms or hydroxyl groups, W2 is one or more divalent organic groups which may also contain fluorine atoms or hydroxyl groups, and at least one of W1 and W2 contains one or more fluorine atoms, and at least one of W1 and W2 contains one or more hydroxyl groups.
[0637] [Chemistry 80]
[0638]
[0639] In the formula, W3 is one or more tetravalent organic groups which may contain fluorine atoms, W4 is one or more divalent organic groups which may contain fluorine atoms, and at least one of W3 and W4 contains one or more fluorine atoms.
[0640] [Chemistry 81]
[0641]
[0642] In the formula, W5 is one or more tetravalent organic groups which may contain a hydroxyl group, W6 is one or more divalent organic groups which may contain a hydroxyl group, and at least one of W5 and W6 contains one or more hydroxyl groups.
[0643] [Chemistry 82]
[0644]
[0645] [Chemistry 83]
[0646]
[0647] In the formula, R1 is any one of the groups represented by the following formula (1D), and two or more types of R1 may be used in combination.
[0648] [Chemistry 84]
[0649]
[0650] [2]: The protective film forming composition for alkaline hydrogen peroxide water as described in [1], wherein W2 in the general formula (1A) contains at least one fluorine atom and a hydroxyl group.
[0651] [3]: The protective film-forming composition for alkaline hydrogen peroxide water as described in [1] or [2], wherein W2 in the general formula (1A) is a group represented by the following general formula (1E),
[0652] [Chemistry 85]
[0653]
[0654] [4]: The protective film-forming composition for alkaline hydrogen peroxide solution of [1], [2] or [3], wherein W1 in the general formula (1A) is any one of the groups represented by the following general formula (1F),
[0655] [Chemistry 86]
[0656]
[0657] [5]: The protective film-forming composition for alkaline hydrogen peroxide solution of [1], [2], [3] or [4], further comprising as component (A') a polymer (IV) having a repeating unit represented by the following general formula (4A) and a terminal group represented by the following general formula (2C),
[0658] [Chemistry 87]
[0659]
[0660] In the formula, W7 is a tetravalent organic group, and W8 is a divalent organic group.
[0661] [Chemistry 88]
[0662]
[0663] In the formula, R2 represents a monovalent organic group having 1 to 10 carbon atoms, n1 represents an integer of 0 or 1, n2 and n3 are 1≤n2≤6 and 0≤n3≤6, and satisfy the relationship of 1≤n2+n3≤6.
[0664] [6]: The composition for forming a protective film against alkaline hydrogen peroxide solution according to [1], [2], [3], [4] or [5], wherein the weight average molecular weight of the component (A) is 1,000 to 10,000.
[0665] [7]: A protective film forming composition for alkaline hydrogen peroxide water as described in [1], [2], [3], [4], [5] or [6], wherein the component (B) is a mixture of one or more organic solvents having a boiling point of less than 180°C and one or more organic solvents having a boiling point of 180°C or more.
[0666] [8]: A protective film forming composition for alkaline hydrogen peroxide water as described in [1], [2], [3], [4], [5], [6] or [7], wherein the protective film forming composition further contains one or more of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer.
[0667] [9]: A protective film forming composition for alkaline hydrogen peroxide solution as described in [1], [2], [3], [4], [5], [6], [7] or [8], wherein the protective film forming composition provides a protective film that is resistant to hydrogen peroxide solution containing ammonia.
[0668]
[10] : A protective film forming composition for alkaline hydrogen peroxide water as described in [9], wherein when a silicon substrate on which the protective film has been formed is immersed in 1.0 mass % hydrogen peroxide water containing 0.5 mass % ammonia at 70°C for 5 minutes, no peeling of the protective film is observed.
[0669]
[11] : A substrate for manufacturing a semiconductor device, characterized in that a protective film obtained by curing a protective film forming composition such as [1], [2], [3], [4], [5], [6], [7], [8], [9], or
[10] is formed on the substrate.
[0670]
[12] : A method for forming a protective film used in a manufacturing step of a semiconductor device, characterized by:
[0671] A protective film forming composition such as [1], [2], [3], [4], [5], [6], [7], [8], [9], or
[10] is spin-coated on a substrate to be processed, and the substrate to be processed coated with the protective film forming composition is subjected to heat treatment in an inert gas environment at a temperature in the range of 50°C to 600°C for 10 seconds to 7200 seconds to obtain a cured film.
[0672]
[13] : A method for forming a protective film used in a manufacturing step of a semiconductor device, characterized by:
[0673] A protective film forming composition such as [1], [2], [3], [4], [5], [6], [7], [8], [9], or
[10] is spin-coated on a substrate to be processed, and the substrate to be processed coated with the protective film forming composition is heat-treated in air at a temperature in the range of 50°C to 250°C for 5 seconds to 600 seconds to form a coating film, and then heat-treated in an inert gas environment at a temperature in the range of 200°C to 600°C for 10 seconds to 7200 seconds to obtain a cured film.
[0674]
[14] : The method for forming a protective film as described in
[12] or
[13] , wherein the oxygen concentration in the inert gas is 1% or less.
[0675]
[15] : A method for forming a protective film as described in
[12] ,
[13] , or
[14] , wherein a substrate to be processed has a structure with a height of 30 nm or more or a height difference as the substrate to be processed.
[0676]
[16] : A pattern forming method is a method for forming a pattern on a processed substrate, characterized by comprising the following steps:
[0677] (I-1) forming a protective film on a substrate to be processed using a protective film forming composition as described in [1], [2], [3], [4], [5], [6], [7], [8], [9] or
[10] ,
[0678] (I-2) forming a silicon-containing resist interlayer film on the protective film using a silicon-containing resist interlayer film material,
[0679] (I-3) forming a resist upper layer film on the silicon-containing resist intermediate film using a photoresist composition,
[0680] (I-4) forming a circuit pattern on the resist upper layer film,
[0681] (I-5) using the patterned resist upper layer film as a mask to transfer the pattern to the silicon-containing resist intermediate film by etching,
[0682] (I-6) using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask to etch and transfer the pattern to the protective film, and
[0683] (I-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0684]
[17] : A pattern forming method is a method for forming a pattern on a processed substrate, characterized by comprising the following steps:
[0685] (II-1) forming a protective film on a substrate to be processed using a protective film forming composition as described in [1], [2], [3], [4], [5], [6], [7], [8], [9] or
[10] ,
[0686] (II-2) forming a silicon-containing resist interlayer film on the protective film using a silicon-containing resist interlayer film material,
[0687] (II-3) forming an organic antireflection film on the silicon-containing resist intermediate film,
[0688] (II-4) forming a resist upper layer film on the organic antireflection film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film,
[0689] (II-5) using the patterned resist upper layer film as a mask to etch and transfer the pattern to the organic anti-reflection film and the silicon-containing resist intermediate film,
[0690] (II-6) using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask to etch and transfer the pattern to the protective film, and
[0691] (II-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0692]
[18] : A pattern forming method is a method for forming a pattern on a processed substrate, characterized by comprising the following steps:
[0693] (III-1) forming a protective film on a substrate to be processed using a protective film forming composition as described in [1], [2], [3], [4], [5], [6], [7], [8], [9] or
[10] ,
[0694] (III-2) forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the protective film,
[0695] (III-3) forming a resist upper layer film on the inorganic hard mask using a photoresist composition,
[0696] (III-4) forming a circuit pattern on the resist upper layer film,
[0697] (III-5) using the patterned resist upper layer film as a mask to transfer the pattern to the inorganic hard mask by etching,
[0698] (III-6) using the inorganic hard mask film with the transferred pattern as a mask to etch and transfer the pattern to the protective film, and
[0699] (III-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0700]
[19] : A pattern forming method is a method for forming a pattern on a processed substrate, characterized by comprising the following steps:
[0701] (IV-1) forming a protective film on a substrate to be processed using a protective film forming composition as described in [1], [2], [3], [4], [5], [6], [7], [8], [9] or
[10] ,
[0702] (IV-2) forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the protective film,
[0703] (IV-3) forming an organic antireflection film on the inorganic hard mask film,
[0704] (IV-4) forming a resist upper layer film on the organic antireflection film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film,
[0705] (IV-5) using the patterned resist upper layer film as a mask to etch and transfer the pattern to the organic antireflection film and the inorganic hard mask,
[0706] (IV-6) using the inorganic hard mask having the transferred pattern as a mask to etch and transfer the pattern to the protective film, and
[0707] (IV-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
[0708]
[20] : The pattern forming method of
[18] or
[19] , wherein the inorganic hard mask is formed by a CVD method or an ALD method.
[0709]
[21] : A pattern forming method as described in
[16] or
[17] , wherein after step (I-6) or step (II-6), there is further a step of removing the silicon-containing resist intermediate film of the transferred pattern by wet etching using alkaline hydrogen peroxide solution.
[0710]
[22] : A pattern forming method as described in
[16] ,
[17] ,
[18] ,
[19] or
[20] , wherein the step (I-7), step (II-7), step (III-7) or step (IV-7) comprises a step of transferring the pattern to the processed substrate by wet etching using alkaline hydrogen peroxide solution using the protective film to which the transferred pattern has been applied as a mask.
[0711]
[23] : A pattern forming method as described in
[16] ,
[17] ,
[18] ,
[19] or
[20] , wherein step (I-7), step (II-7), step (III-7) or step (IV-7) comprises a step of using the protective film of the transferred pattern as a mask to perform ion implantation to pattern the processed substrate.
[0712]
[24] : A pattern forming method as in
[23] , wherein, after the step of patterning the processed substrate by ion implantation, there is further a step of removing the silicon-containing resist intermediate film of the transferred pattern by wet etching using alkaline hydrogen peroxide water.
[0713]
[25] : A pattern forming method as described in
[16] ,
[17] ,
[18] ,
[19] ,
[20] ,
[21] ,
[22] ,
[23] , or
[24] , wherein the circuit pattern is formed by photolithography using light with a wavelength of not less than 10 nm and not more than 300 nm, direct drawing using an electron beam, nano-molding, or a combination thereof.
[0714]
[26] : A pattern forming method as described in
[16] ,
[17] ,
[18] ,
[19] ,
[20] ,
[21] ,
[22] ,
[23] ,
[24] or
[25] , wherein the circuit pattern is formed by developing the circuit pattern using an alkali developer or an organic solvent.
[0715]
[27] : A pattern forming method as described in
[16] ,
[17] ,
[18] ,
[19] ,
[20] ,
[21] ,
[22] ,
[23] ,
[24] ,
[25] , or
[26] , which uses a semiconductor device substrate, or a substrate on which a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film is formed as the processed substrate.
[0716]
[28] : A pattern forming method as in
[27] , which uses a substrate containing silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof as the processed substrate.
[0717] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and any device having substantially the same configuration and exhibiting the same function and effect as the technical concept described in the claims of the present invention is included in the technical scope of the present invention.
[0718] Description of Reference Numerals
[0719] 1:Substrate
[0720] 2: Processing layer
[0721] 2a: Pattern (pattern formed by the processed layer)
[0722] 3: Protective film
[0723] 3': Protective film forming composition
[0724] 3a: Protective film pattern
[0725] 4: Silicon-containing resist interlayer
[0726] 4a: Silicon-containing resist interlayer pattern
[0727] 5: Resist upper film
[0728] 5a: Resist upper film pattern
[0729] 6: Exposure part
[0730] 7: Base substrate with dense hole pattern
[0731] 8: Protective film
[0732] 9: Base substrate with large isolated trench patterns
[0733] 10: Protective film
[0734] delta10: height difference between the trench part and the non-trench part of the protective film 10
Claims
1. A protective film-forming composition for alkaline hydrogen peroxide solution, characterized in that it contains: (A) a polymer having fluorine atoms and hydroxyl groups represented by any one of the following (I) and (II), or a mixture of a polymer having fluorine atoms and a polymer having hydroxyl groups represented by the following (III), and (B) an organic solvent, further comprising as component (A') a polymer (IV) having a repeating unit represented by the following general formula (4A) and a terminal group represented by the following formula (2C-1), wherein the amount of polymer (IV) is 1 to 10 parts by mass based on 100 parts by mass of component (A), (I) A polymer having a repeating unit represented by the following general formula (1A) containing at least one fluorine atom and a hydroxyl group and having a terminal group represented by any one of the following general formulas (1B) and (1C), (II) a polymer having a repeating unit containing at least one fluorine atom represented by the following general formula (2A) and a repeating unit containing at least one hydroxyl group represented by the following general formula (3A), and the terminal group is a group represented by any one of the following general formulas (1B) and (1C), (III) a mixture of a polymer having a repeating unit containing at least one fluorine atom represented by the following general formula (2A) and having a terminal group represented by any one of the following general formulas (1B) and (1C), and a polymer having a repeating unit containing at least one hydroxyl group represented by the following general formula (3A) and having a terminal group represented by any one of the following general formulas (1B) and (1C), In the formula, W1 is any one of the following groups: W2 is any one of the following groups: and at least one of W1 and W2 contains one or more fluorine atoms, and at least one of W1 and W2 contains one or more hydroxyl groups, In the formula, W3 is one or more tetravalent organic groups which may contain fluorine atoms, W4 is one or more divalent organic groups which may contain fluorine atoms, and at least one of W3 and W4 contains one or more fluorine atoms. In the formula, W5 is one or more tetravalent organic groups which may contain a hydroxyl group, W6 is one or more divalent organic groups which may contain a hydroxyl group, and at least one of W5 and W6 contains one or more hydroxyl groups. In the formula, R1 is any one of the groups represented by the following formula (1D), and two or more R1s may be used in combination. In the formula, W7 is any one of the following groups: W8 is any one of the following groups: In the formula, R2 represents a monovalent organic group having 1 to 10 carbon atoms.
2. The protective film-forming composition for alkaline hydrogen peroxide water according to claim 1, wherein: W2 in the general formula (1A) is a group represented by the following general formula (1E), 3. The protective film-forming composition for alkaline hydrogen peroxide water according to claim 1 or 2, wherein: W1 in the general formula (1A) is any one of the groups represented by the following general formula (1F), 4. The protective film-forming composition for alkaline hydrogen peroxide water according to claim 1 or 2, wherein: The weight average molecular weight of the component (A) is 1,000 to 10,000.
5. The protective film-forming composition for alkaline hydrogen peroxide water according to claim 1 or 2, wherein: The component (B) is a mixture of one or more organic solvents having a boiling point of less than 180°C and one or more organic solvents having a boiling point of 180°C or higher.
6. The protective film-forming composition for alkaline hydrogen peroxide water according to claim 1 or 2, wherein: The protective film forming composition further contains one or more of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer.
7. The protective film-forming composition for alkaline hydrogen peroxide water according to claim 1 or 2, wherein: The protective film forming composition provides a protective film that is resistant to hydrogen peroxide water containing ammonia.
8. The protective film-forming composition for alkaline hydrogen peroxide water according to claim 7, wherein: When the protective film-forming composition was used and a silicon substrate on which the protective film was formed was immersed in 1.0 mass % hydrogen peroxide water containing 0.5 mass % ammonia at 70° C. for 5 minutes, no peeling of the protective film was observed.
9. A substrate for manufacturing a semiconductor device, characterized by: A protective film obtained by curing the protective film-forming composition according to claim 1 or 2 is formed on a substrate.
10. A method for forming a protective film, which is a method for forming a protective film used in a manufacturing step of a semiconductor device, characterized by: The protective film forming composition according to claim 1 is spin-coated on a substrate to be processed, and the substrate coated with the protective film forming composition is heat-treated at a temperature of 50° C. to 600° C. for 10 seconds to 7200 seconds in an inert gas environment to obtain a cured film.
11. A method for forming a protective film, which is a method for forming a protective film used in a manufacturing step of a semiconductor device, characterized by: The protective film forming composition according to claim 1 is spin-coated on a substrate to be processed, and the substrate to be processed coated with the protective film forming composition is heat-treated in air at a temperature in the range of 50° C. to 250° C. for 5 seconds to 600 seconds to form a coating film, and then heat-treated in an inert gas environment at a temperature in the range of 200° C. to 600° C. for 10 seconds to 7200 seconds to obtain a cured film.
12. The method for forming a protective film according to claim 10 or 11, wherein: The oxygen concentration in the inert gas is 1% or less. 13 . The method for forming a protective film according to claim 10 , wherein a substrate to be processed having a structure or a height difference of 30 nm or more is used as the substrate to be processed.
14. A method for forming a pattern on a processed substrate, characterized by comprising the following steps: (I-1) forming a protective film on a substrate to be processed using the protective film forming composition according to claim 1, (I-2) forming a silicon-containing resist intermediate film on the protective film using a silicon-containing resist intermediate film material, (I-3) forming a resist upper layer film on the silicon-containing resist intermediate film using a photoresist composition, (I-4) forming a circuit pattern on the resist upper layer film, (I-5) using the patterned resist upper layer film as a mask to transfer the pattern to the silicon-containing resist intermediate film by etching, (I-6) using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask to etch and transfer the pattern to the protective film, and (I-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
15. A method for forming a pattern on a processed substrate, characterized by comprising the following steps: (II-1) forming a protective film on a substrate to be processed using the protective film forming composition according to claim 1, (II-2) forming a silicon-containing resist interlayer film on the protective film using a silicon-containing resist interlayer film material, (II-3) forming an organic antireflection film on the silicon-containing resist intermediate film, (II-4) forming a resist upper layer film on the organic antireflection film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film, (II-5) using the patterned resist upper layer film as a mask to etch and transfer the pattern to the organic anti-reflection film and the silicon-containing resist intermediate film, (II-6) using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask to etch and transfer the pattern to the protective film, and (II-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
16. A method for forming a pattern on a processed substrate, characterized by comprising the following steps: (III-1) forming a protective film on a substrate to be processed using the protective film forming composition according to claim 1, (III-2) forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the protective film, (III-3) forming a resist upper layer film on the inorganic hard mask using a photoresist composition, (III-4) forming a circuit pattern on the resist upper layer film, (III-5) using the patterned resist upper layer film as a mask to transfer the pattern to the inorganic hard mask by etching, (III-6) using the inorganic hard mask film with the transferred pattern as a mask to etch and transfer the pattern to the protective film, and (III-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed.
17. A method for forming a pattern on a processed substrate, characterized by comprising the following steps: (IV-1) forming a protective film on a substrate to be processed using the protective film forming composition according to claim 1, (IV-2) forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the protective film, (IV-3) forming an organic antireflection film on the inorganic hard mask film, (IV-4) forming a resist upper layer film on the organic antireflection film using a photoresist composition to form a four-layer film structure, and forming a circuit pattern on the resist upper layer film, (IV-5) using the patterned resist upper layer film as a mask to etch and transfer the pattern to the organic antireflection film and the inorganic hard mask, (IV-6) using the inorganic hard mask having the transferred pattern as a mask to etch and transfer the pattern to the protective film, and (IV-7) Using the protective film to which the pattern has been transferred as a mask, a pattern is formed on the substrate to be processed. 18 . The pattern forming method according to claim 16 , wherein the inorganic hard mask is formed by a CVD method or an ALD method.
19. The pattern forming method according to claim 14 or 15, wherein: After the step (I-6) or the step (II-6), there is further a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide solution.
20. The pattern forming method according to any one of claims 14 to 17, wherein: The step (I-7), step (II-7), step (III-7), or step (IV-7) includes a step of transferring the pattern to the processed substrate by wet etching using alkaline hydrogen peroxide solution, using the protective film to which the transferred pattern has been applied as a mask.
21. The pattern forming method according to any one of claims 14 to 17, wherein: The step (I-7), step (II-7), step (III-7) or step (IV-7) includes a step of performing ion implantation using the protective film to which the transferred pattern has been applied as a mask to perform pattern processing on the substrate to be processed.
22. The pattern forming method according to claim 21, wherein: After the step of patterning the substrate to be processed by ion implantation, there is further a step of removing the silicon-containing resist intermediate film to which the pattern has been transferred by wet etching using alkaline hydrogen peroxide water.
23. The pattern forming method according to any one of claims 14 to 17, wherein: The circuit pattern is formed by photolithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nano-molding, or a combination thereof.
24. The pattern forming method according to any one of claims 14 to 17, wherein: The circuit pattern is formed by developing the circuit pattern using an alkali developer or an organic solvent.
25. A pattern forming method according to any one of claims 14 to 17, which uses a semiconductor device substrate, or a substrate on which a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film is formed as the processed substrate.
26. The pattern forming method according to claim 25, wherein a substrate containing silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof is used as the processed substrate.
Citation Information
Patent Citations
Method and device for forming silicon nitride film, and method for preprocessing of cleaning thereof
JP2002334869A
Photoresist underlayer film forming material and pattern forming method
JP2007199653A
New photoacid generator, resist material using the same, and pattern forming method
JP2009269953A
Underlayer film forming composition for lithography
JP2010122297A
Resist underlayer film-forming composition for lithography comprising resin containing polyimide structure
JP2013137334A